Thermoplastic polymer particles and methods of making and using same - Patents.com

JP7643847B2Active Publication Date: 2025-03-11XEROX CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020138469
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-30
Filing Date
2020-08-19
Publication Date
2025-03-11
Estimated Expiration
2040-08-19

Smart Images

  • Figure 0007643847000019
    Figure 0007643847000019
  • Figure 0007643847000020
    Figure 0007643847000020
  • Figure 0007643847000021
    Figure 0007643847000021
Patent Text Reader

Abstract

To provide a thermoplastic polymer particle composition comprising a thermoplastic polymer and an emulsion stabilizer associated with an outer surface of the polymer particle, and a production method of the composition.SOLUTION: A composition is provided, which comprises particles comprising a thermoplastic polymer, and an emulsion stabilizer associated with an outer surface of the particles, where the particles have a circularity of about 0.90 to about 1.0. A method is provided, which includes: mixing a mixture comprising a thermoplastic polymer, a dispersion medium that is immiscible with the thermoplastic polymer, and the emulsion stabilizer at a temperature greater than a melting point or softening temperature of the thermoplastic polymer and at a shear rate sufficiently high to disperse the thermoplastic polymer in the dispersion medium; cooling the mixture to below the melting point or softening temperature of the thermoplastic polymer to form solidified particles comprising the thermoplastic polymer, and the emulsion stabilizer associated with the outer surface of the solidified particles; and separating the solidified particles from the dispersion medium.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to thermoplastic polymer particles and methods for making such particles. Such particles, particularly highly spherical thermoplastic polymer particles, can be useful, inter alia, as starting materials for additive manufacturing. [Background technology]

[0002] Three-dimensional (3D) printing, also known as additive manufacturing, is a rapidly growing technology field. While 3D printing has traditionally been used for rapid prototyping tasks, the technique is increasingly being adopted for the production of commercial and industrial objects that may have completely different structural and mechanical tolerances than the rapid prototype.

[0003] 3D printing operates by depositing either (a) droplets or streams of molten or solidifiable material, or (b) powder particulates at precise deposition locations for subsequent solidification, into larger objects that may have any number of complex shapes. Such deposition and solidification processes are typically performed under computer control to result in layer-by-layer building of larger objects. In certain examples, the consolidation of powder particulates may occur in a 3D printing system that uses a laser to facilitate selective laser sintering (SLS). Incomplete layer-to-layer fusion may lead to structural weaknesses, which can be problematic for printing objects with tight structural and mechanical tolerances.

[0004] Powder particulates that can be used in 3D printing include thermoplastic polymers, including thermoplastic elastomers, metals, and other solidifiable materials. A wide array of thermoplastic polymers are known, but relatively few have suitable properties for use in 3D printing, especially when using powder bed fusion (PBF). Additive manufacturing methods that use powder materials include PBF, selective laser sintering (SLS), selective heat sintering (SHM), selective laser melting (SLM), electron beam melting (EBM), binder jetting, and multi jet fusion (MJF). In SLS printing methods, particles are fused together by energy from a high-powered laser. Typical thermoplastic polymers suitable for use in 3D printing include those that have a sharp melting point and a recrystallization point that is approximately 20°C to 50°C below the melting point. This difference may allow more effective coalescence between adjacent polymer layers to occur, thereby promoting improved structural and mechanical integrity.

[0005] To achieve good printing performance using powder particulates, especially polymer powder particulates, the powder particulates need to maintain good flow properties in the solid state. Flow properties can be evaluated, for example, by measuring the percentage of powder particulates from a sample that can pass through a standard sieve of a certain size and / or by measuring the angle of repose. A high percentage of sieveable powder particulates can indicate that the particulates are present as substantially individual particles without agglomeration, which can be a characteristic of easy powder flow. In contrast, a low value of the angle of repose can be a characteristic of powder flowability. A relatively narrow particle size distribution and regularity of particle shape in a sample can also help promote good powder flow performance.

[0006] Commercially available powder particulates are often obtained by cryogenic grinding or precipitation processes, which can result in irregular particle shapes and wide particle size distributions. Irregular particle shapes can reduce powder flow performance during the 3D printing process. In addition, powder particulates with shape irregularities, especially those obtained from current commercial processes, can result in poor packing efficiency following deposition and consolidation, which can result in extensive void formation within the printed object because the powder particulates are not closely packed during deposition. Wide particle size distributions can be problematic in this regard as well. Poor powder flow performance can be addressed to some extent by dry blending with fillers and flow aids, but these techniques can have limited effectiveness with softer polymeric materials such as elastomers due to particle agglomeration. Summary of the Invention

[0007] The present disclosure relates to thermoplastic polymer particles and methods for making such particles. Such particles, particularly highly spherical thermoplastic polymer particles, can be useful, inter alia, as starting materials for additive manufacturing.

[0008] Provided herein is a composition that includes a particle that includes a thermoplastic polymer and an emulsion stabilizer (eg, nanoparticles and / or surfactant) associated with the outer surface of the particle.

[0009] Described herein is a method that includes mixing a mixture comprising a thermoplastic polymer, a dispersion medium that is immiscible with the thermoplastic polymer, and an emulsion stabilizer (e.g., nanoparticles and / or surfactant) at a temperature above the melting point or softening temperature of the thermoplastic polymer and at a shear rate high enough to disperse the thermoplastic polymer in the dispersion medium, cooling the mixture below the melting point or softening temperature of the thermoplastic polymer to form solidified particles comprising the thermoplastic polymer and the emulsion stabilizer associated with an outer surface of the solidified particles, and separating the solidified particles from the dispersion medium. [Brief description of the drawings]

[0010] The following figures are included to illustrate certain aspects of the embodiments and should not be viewed as exclusive embodiments. The disclosed subject matter is capable of considerable modification, alteration, combinations, and equivalents in form and function, as will occur to those skilled in the art and having the benefit of this disclosure.

[0011] [Figure 1] 1 is a flow chart of a non-limiting exemplary method 100 of the present disclosure. [Diagram 2] 1 is a scanning electron microscope photograph of polyamide particles. [Diagram 3] 1 is a scanning electron microscope photograph of polyamide particles. [Figure 4] 1 is a scanning electron microscope photograph of polyamide particles. [Diagram 5] 1 is a scanning electron microscope photograph of polyamide particles. [Figure 6] 1 is a scanning electron microscope photograph of polyamide particles. [Figure 7] 1 is a scanning electron microscope photograph of polyamide particles. [Figure 8] 1 is a scanning electron microscope photograph of polyamide particles. [Figure 9] 1 is a scanning electron microscope photograph of polyamide particles. [Figure 10] 1 is a scanning electron microscope photograph of polyamide particles. [Figure 11] 1 is a scanning electron microscope photograph of polyamide particles. [Figure 12] 1 is a scanning electron microscope photograph of polyamide particles. [Figure 13] 1 is a scanning electron microscope photograph of polyamide particles. [Figure 14] 1 is a scanning electron microscope photograph of polyamide particles. [Figure 15] 1 is a scanning electron microscope photograph of polyamide particles. [Figure 16] 1 is a scanning electron microscope photograph of polyamide particles. [Figure 17] 1 is a scanning electron microscope photograph of polyamide particles. [Figure 18]1 is a scanning electron microscope photograph of polyamide particles. [Figure 19] 1 is a scanning electron microscope photograph of polyamide particles. [Figure 20] 1 is a scanning electron microscope photograph of polyamide particles. [Figure 21] 1 is a scanning electron microscope photograph of polyamide particles. [Figure 22] 1 is a scanning electron microscope photograph of polyamide particles. [Figure 23-1] 1 is a scanning electron microscope photograph of polyamide particles. [Figure 23-2] 1 is a scanning electron microscope photograph of polyamide particles. [Figure 24] 1 is a scanning electron microscope photograph of polyamide particles. [Diagram 25] 1 shows the volume density particle size distribution of screened and unscreened particles, respectively. [Figure 26] 1 shows the volume density particle size distribution of screened and unscreened particles, respectively. [Figure 27] 1 shows an exemplary optical microscope image at 150X magnification of thermoplastic polyurethane microparticles. [Figure 28] 1 shows an exemplary optical microscope image of thermoplastic polyurethane microparticles. [Figure 29A] 4 shows exemplary SEM images of the thermoplastic polyurethane microparticles obtained in Comparative Example 2 at various magnifications. [Figure 29B] 4 shows exemplary SEM images of the thermoplastic polyurethane microparticles obtained in Comparative Example 2 at various magnifications. [Diagram 30] 1 shows an exemplary optical microscope image of thermoplastic polyurethane microparticles. [Diagram 31] 1 shows an exemplary histogram of particle size for thermoplastic polyurethane microparticles. [Diagram 32] 1 shows an exemplary optical microscope image of thermoplastic polyurethane microparticles. [Diagram 33] 1 shows an exemplary histogram of particle size for thermoplastic polyurethane microparticles. [Diagram 34] 1 shows an exemplary optical microscope image of thermoplastic polyurethane microparticles. [Figure 35A] 1 shows exemplary SEM images of thermoplastic polyurethane microparticles at various magnifications. [Figure 35B] 1 shows exemplary SEM images of thermoplastic polyurethane microparticles at various magnifications. [Diagram 36] 1 shows an exemplary histogram of particle size for thermoplastic polyurethane microparticles. [Figure 37] 1 shows an exemplary optical microscope image of thermoplastic polyurethane microparticles. [Figure 38A] 1 shows exemplary SEM images of thermoplastic polyurethane microparticles at various magnifications. [Figure 38B] 1 shows exemplary SEM images of thermoplastic polyurethane microparticles at various magnifications. [Figure 38C] 1 shows exemplary SEM images of thermoplastic polyurethane microparticles at various magnifications. [Figure 38D] 1 shows exemplary SEM images of thermoplastic polyurethane microparticles at various magnifications. [Figure 39] 1 shows an exemplary histogram of particle size for thermoplastic polyurethane microparticles. [Diagram 40] 1 shows an exemplary optical microscope image of thermoplastic polyurethane microparticles. [Figure 41A] 1 shows exemplary SEM images of thermoplastic polyurethane microparticles at various magnifications. [Figure 41B] 1 shows exemplary SEM images of thermoplastic polyurethane microparticles at various magnifications. [Figure 41C] 1 shows exemplary SEM images of thermoplastic polyurethane microparticles at various magnifications. [Diagram 42] 1 shows an exemplary histogram of particle size for thermoplastic polyurethane microparticles. [Figure 43A] 1 shows an exemplary SEM image of TPU 90A NAT thermoplastic polyurethane particulate (ADVANC3D). [Figure 43B] 1 shows an exemplary SEM image of TPU 90A NAT thermoplastic polyurethane particulate (ADVANC3D). [Figure 43C] 1 shows an exemplary SEM image of TPU 90A NAT thermoplastic polyurethane particulate (ADVANC3D). [Fig. 43D] 1 shows an exemplary SEM image of TPU 90A NAT thermoplastic polyurethane particulate (ADVANC3D). [Figure 43E] 1 shows an exemplary SEM image of TPU 90A NAT thermoplastic polyurethane particulate (ADVANC3D). [Diagram 44] 1 shows an optical image of a print obtained from thermoplastic polyurethane microparticles. [Diagram 45] 1 shows an exemplary optical microscope image at 150X magnification of thermoplastic polyurethane microparticles. [Figure 46] 1 shows an exemplary histogram of particle size for thermoplastic polyurethane microparticles. [Figure 47] 1 shows an exemplary optical microscope image at 150X magnification of thermoplastic polyurethane microparticles. [Figure 48A] 1 shows exemplary SEM images of thermoplastic polyurethane microparticles at various magnifications. [Figure 48B] 1 shows exemplary SEM images of thermoplastic polyurethane microparticles at various magnifications. [Figure 49] 1 shows an exemplary histogram of particle size for thermoplastic polyurethane microparticles. [Figure 50] An exemplary optical microscope image at 100X magnification of the resulting thermoplastic polyurethane microparticles is shown. [Figure 51] 1 shows an exemplary histogram of particle size for thermoplastic polyurethane microparticles. [Figure 52] 1 shows an exemplary optical microscope image at 100X magnification of thermoplastic polyurethane microparticles. [Figure 53] 1 shows an exemplary histogram of particle size for thermoplastic polyurethane microparticles. [Figure 54] 1 shows an exemplary optical microscope image at 300X magnification of thermoplastic polyurethane microparticles. [Figure 55] 1 shows an exemplary histogram of particle size for thermoplastic polyurethane microparticles. [Figure 56] 1 shows an exemplary optical microscope image at 150X magnification of thermoplastic polyurethane microparticles. [Figure 57] 1 shows an exemplary histogram of particle size for thermoplastic polyurethane microparticles. [Figure 58] 1 shows an exemplary optical microscope image at 150X magnification of thermoplastic polyurethane microparticles. [Figure 59] 1 shows an exemplary histogram of particle size for thermoplastic polyurethane microparticles. [Figure 60] 1 shows an exemplary optical microscope image at 150X magnification of thermoplastic polyurethane microparticles. [Figure 61A] 1 shows exemplary SEM images of thermoplastic polyurethane microparticles at various magnifications. [Figure 61B] 1 shows exemplary SEM images of thermoplastic polyurethane microparticles at various magnifications. [Figure 62] 1 shows an exemplary histogram of particle size for thermoplastic polyurethane microparticles. [Figure 63] 1 shows an exemplary optical microscope image at 150X magnification of thermoplastic polyurethane microparticles. [Figure 64] 1 shows an exemplary histogram of particle size for thermoplastic polyurethane microparticles. [Figure 65] 1 shows an exemplary particle size distribution plot of thermoplastic polyurethane microparticles. [Figure 66] 1 shows an optical image of the print. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present disclosure relates to thermoplastic polymer particles and methods for making such particles. Such particles, particularly highly spherical thermoplastic polymer particles, can be useful, inter alia, as starting materials for additive manufacturing.

[0013] More specifically, the thermoplastic polymer particles described herein are produced by a melt-emulsion process, in which a thermoplastic polymer is dispersed as a melt in a dispersing medium that is immiscible with the thermoplastic polymer. A sufficient amount of shear is used to cause the thermoplastic polymer melt to form droplets in the dispersing medium. The emulsion stabilizer (e.g., nanoparticles and / or surfactants, in some cases including one or more members of each type) provides surface tension at the phase interface between the dispersing medium and the thermoplastic polymer melt. Once the melt-emulsion process is complete, the dispersion is cooled to solidify the polymer into thermoplastic polymer particles.

[0014] Without being bound by theory, during the melt-emulsification process, the emulsion stabilizer is primarily present at the interface between the polymer melt and the dispersion medium. As a result, when the mixture is cooled, the emulsion stabilizer remains at said interface. Advantageously, the emulsion stabilizer on the surface of the resulting particles can aid in the flow properties of the resulting particles.

[0015] As previously mentioned, conventional methods of forming thermoplastic polymer particles with good flowability include at least two steps, including first forming and purifying the particles (e.g., by cryogenic grinding or precipitation processes) and second coating the particles to some extent with a flow promoter such as nanoparticulate silica, carbon black, or PTFE particles. The methods described herein advantageously produce thermoplastic polymer particles with a coating that improves the flowability of the particles in one process.

[0016] Additionally, without wishing to be bound by theory, it is believed that the methods of the present disclosure may produce particles with a more uniform coverage of the emulsion stabilizer, further improving flowability, which is particularly advantageous in additive manufacturing applications such as 3D printing.

[0017] Definitions and Test Methods As used herein, the term "immiscible" refers to a mixture of components that, when combined, form two or more phases that have a melting point of less than 5% by weight with each other at room temperature at ambient pressure, or at the melting point of the components if solid at room temperature. For example, polyethylene oxide with a molecular weight of 10,000 g / mol is solid at room temperature and has a melting point of 65°C. Thus, if a material is liquid at room temperature and the polyethylene oxide has a melting point of less than 5% by weight at 65°C, the polyethylene oxide is immiscible with the material.

[0018] As used herein, the term "thermoplastic polymer" refers to a plastic polymeric material that reversibly softens and hardens on heating and cooling. Thermoplastic polymers include thermoplastic elastomers.

[0019] As used herein, the term "elastomer" refers to a copolymer that includes a crystalline "hard" segment and an amorphous "soft" segment. In the case of polyurethanes, the crystalline segment may include the portion of the polyurethane that includes urethane functionality and optional chain extenders, and the soft segment may include, for example, a polyol.

[0020] As used herein, the term "polyurethane" refers to the polymeric reaction product between a diisocyanate, a polyol, and an optional chain extender.

[0021] As used herein, the term "oxide" refers to both metal oxides and non-metal oxides. For purposes of this disclosure, silicon is considered to be a metal.

[0022] As used herein, the terms "associated," "association," and grammatical variations thereof between an emulsion stabilizer and a surface refer to chemical bonding and / or physical adhesion of the emulsion stabilizer to the surface. Without being bound by theory, the association described herein between the polymer and the emulsion stabilizer is believed to be primarily a physical adherence, via hydrogen bonding and / or other mechanisms. However, some degree of chemical bonding may occur.

[0023] As used herein, the term "embedded" with respect to the surface of nanoparticles and polymer particles refers to the nanoparticles extending at least partially into the surface such that the polymer comes into contact with the nanoparticles to a greater extent than if the nanoparticles were simply placed on the surface of the polymer particle.

[0024] In this specification, D10, D50, D90, and diameter span are mainly used in this specification to describe particle size. As used in this specification, the term "D10" refers to a diameter, and 10% of the sample (by volume, unless otherwise stated) is made up of particles with a diameter less than the diameter value. As used in this specification, the term "D50" refers to a diameter, and 50% of the sample (by volume, unless otherwise stated) is made up of particles with a diameter less than the diameter value. As used in this specification, the term "D90" refers to a diameter, and 90% of the sample (by volume, unless otherwise stated) is made up of particles with a diameter less than the diameter value.

[0025] As used herein, the terms "diameter span" and "span" and "span size" when referring to diameter provide a measure of the spread of the particle size distribution and are calculated as (D90-D10) / D50 (again, each D value is based on volume unless otherwise noted).

[0026] Particle size may be determined by light scattering techniques using a Malvern MASTERSIZER™ 3000 or analysis of optical digital micrographs. Unless otherwise stated, light scattering techniques are used to analyze particle size.

[0027] For light scattering techniques, the control sample was glass beads with diameters in the range of 15 μm to 150 μm under the trade name Quality Audit Standards QAS4002™ obtained from Malvern Analytical Ltd. Samples were analyzed as dry powders unless otherwise stated. Analyzed particles were dispersed in air and analyzed using the AERO S dry powder dispersion module with the MASTERSIZER™ 3000. Particle size was derived using the instrument software from a plot of volume density as a function of size.

[0028] Particle size measurements and diameter spans can also be determined by optical digital microscopy. Optical images are obtained using a Keyence VHX-2000 digital microscope using version 2.3.5.1 software (system version 1.93) for particle size analysis.

[0029] As used herein, when referring to sieving, the pore size / screen size is described in US Standard Sieves (ASTM E11-17).

[0030] As used herein, the terms "circularity" and "sphericity" for particles refer to how close a particle is to a perfect sphere. To determine circularity, an optical microscope image of the particle is taken. The perimeter (P) and area (A) of the particle in the plane of the microscope image are calculated (e.g., using a SYSMEX FPIA 3000 Particle Shape and Size Analyzer available from Malvern Instruments). The circularity of a particle is expressed as C EA / P and C EA is the circumference of a circle whose area corresponds to the area of ​​the actual particle (A).

[0031] As used herein, the term "sintering window" refers to the difference between the melting temperature (Tm) onset and the crystallization temperature (Tc) onset, i.e., (Tm-Tc) onset. Tm, Tm(onset), Tc, and Tc(onset) are measured by differential scanning calorimetry according to ASTM E794-06(2018) using a heating rate of 10°C / min and a cooling rate of 10°C / min.

[0032] As used herein, the term "shear force" refers to stirring or similar processes that induce mechanical agitation in a fluid.

[0033] As used herein, the term "aspect ratio" refers to the ratio of length divided by width, where the length is greater than the width.

[0034] Unless otherwise stated, the melting points of polymers are determined according to ASTM E794-06(2018) using a heating and cooling rate of 10° C. / min.

[0035] Unless otherwise stated, the softening temperature or softening point of a polymer is determined by ASTM D6090-17. The softening temperature may be measured by using a cup and ball apparatus available from Mettler-Toledo using a 0.50 gram sample at a heating rate of 1° C. / min.

[0036] Angle of repose is a measure of the flowability of a powder. Angle of repose measurements were determined using a Hosokawa Micron Powder Characteristics Tester PT-R using ASTM D6393-14 "Standard Test Method for Bulk Solids Characterized by Carr Indices."

[0037] Hausner ratio (H r ) is a measure of the powder's flowability, and H r =ρ tap / ρ bulk ρ is calculated by bulkis the bulk density according to ASTM D6393-14, and ρ tap is the tap density according to ASTM D6393-14.

[0038] As used herein, the term "embedded" with respect to the surface of nanoparticles and polymer particles refers to the nanoparticles extending at least partially into the surface such that the polymer contacts the nanoparticles to a greater extent than if the nanoparticles were simply layered on the surface of the polymer particle.

[0039] As used herein, the viscosity of a dispersion fluid is the kinematic viscosity at 25° C., as measured by ASTM D445-19, unless otherwise specified. For commercially obtained dispersion fluids (e.g., PDMS oil), the kinematic viscosity data cited herein is that provided by the manufacturer, whether measured according to the aforementioned ASTM or another standard measurement technique.

[0040] Thermoplastic polymer particles and method of manufacture 1 is a flow chart of a non-limiting exemplary method 100 of the present disclosure. A thermoplastic polymer 102, a carrier fluid 104, and an emulsion stabilizer 106 are combined 108 to produce a mixture 110. Components 102, 104, and 106 may be added in any order and may include mixing and / or heating during the process 108 of combining components 102, 104, and 106.

[0041] The mixture 110 is then processed 112 by applying a sufficiently high shear force to the mixture 110 at a temperature above the melting or softening temperature of the thermoplastic polymer 102 to form a melt emulsion 114. Because the temperature is higher than the melting or softening temperature of the thermoplastic polymer 102, the thermoplastic polymer 102 becomes a polymer melt. The shear rate should be sufficient to disperse the polymer melt as droplets (i.e., polymer emulsion 114) in the dispersion medium 104. Without being bound by theory, it is believed that, all other factors being equal, increasing the shear force should decrease the size of the polymer melt droplets in the dispersion medium 104. However, at some point, there may be diminishing returns from increasing the shear force and decreasing the droplet size, or there may be a breakup into droplet contents that reduces the quality of the particles produced.

[0042] The molten emulsion 114 inside and / or outside the mixing vessel is then cooled (116) to solidify the polymer droplets into thermoplastic polymer particles (also referred to as solidified thermoplastic polymer particles). The cooled mixture 118 is then processed (120) to isolate the thermoplastic polymer particles 122 from other components 124 (e.g., the carrier fluid 104, excess emulsion stabilizer 106, etc.) and the thermoplastic polymer particles 122 may be washed or otherwise purified. The thermoplastic polymer particles 122 include the thermoplastic polymer 102 and at least a portion of the emulsion stabilizer 106 coating the outer surface of the thermoplastic polymer particles 122. The emulsion stabilizer 106, or a portion thereof, may be deposited as a uniform coating on the thermoplastic polymer particles 122. In some cases, which may depend on non-limiting factors such as temperature (including cooling rate), type of thermoplastic polymer 102, and type and size of emulsion stabilizer 106, nanoparticles of emulsion stabilizer 106 may become at least partially embedded within the outer surface of thermoplastic polymer particles 122 in the process of associating therewith. Even if the embodiment is not practiced, at least the nanoparticles within emulsion stabilizer 106 may remain tightly associated with thermoplastic polymer particles 122, facilitating their further use. In contrast, dry blending of already formed thermoplastic polymer particulates (e.g., formed by cryogenic grinding or precipitation processes) with a flow aid such as silica nanoparticles does not result in a robust, uniform coating of the flow aid on the thermoplastic polymer particulates.

[0043] Advantageously, the carrier fluids and wash solvents of the systems and methods described herein (e.g., method 101) can be regenerated and reused. Those skilled in the art will recognize any necessary washing of spent carrier fluids and solvents that may be required for the regeneration process.

[0044] The thermoplastic polymer 102 and the dispersion medium 104 should be selected such that the thermoplastic polymer 102 and the dispersion medium 104 are immiscible at various processing temperatures (e.g., from room temperature to the process temperature). An additional factor that may be considered is the difference (e.g., difference or ratio) in viscosity between the molten polyamide 102 and the dispersion medium 104 at the process temperature. The difference in viscosity may affect the droplet breakup and particle size distribution. Without being bound by theory, it is believed that if the viscosities of the molten polyamide 102 and the dispersion medium 104 are too similar, the circularity of the overall product may be reduced, and the particles may become more ovoid and more elongated structures are observed.

[0045] Examples of thermoplastic polymers 102 include, but are not limited to, polyamide, polyurethane, polyethylene, polypropylene, polyacetal, polycarbonate, polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polytrimethylene terephthalate (PTT), polyhexamethylene terephthalate, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyester (e.g., polylactic acid), polyether, polyethersulfone, polyetheretherketone, polyacrylate, polymethacrylate, polyimide, acrylonitrile butadiene styrene (ABS), polyphenylene sulfide, vinyl polymer, polyarylene ether, polyarylene sulfide, polysulfone, polyetherketone, polyamideimide, polyetherimide, polyetherester, polyether block, and polyamide block (PEBA or polyether block amide). copolymers, grafted or ungrafted thermoplastic polyolefins, functionalized or unfunctionalized ethylene / vinyl monomer polymers, functionalized or unfunctionalized ethylene / alkyl (meth)acrylates, functionalized or unfunctionalized (meth)acrylic acid polymers, functionalized or unfunctionalized ethylene / vinyl monomer / alkyl (meth)acrylate terpolymers, ethylene / vinyl monomer / carbonyl terpolymers, ethylene / alkyl (meth)acrylate / carbonyl terpolymers, methyl methacrylate-butadiene-styrene (MBS) type core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymers, chlorinated or chlorosulfonated polyethylene, polyvinylidene fluoride (PVDF), phenolic resins, poly(ethylene / vinyl acetate), polybutadiene, polyisoprene, styrenic block copolymers, polyacrylonitrile, silicones, and the like, and any combination thereof. Copolymers comprising one or more of the foregoing may also be used in the methods and systems of the present disclosure.

[0046] The thermoplastic polymer 102 in the compositions and methods of the present disclosure may be elastomeric or non-elastomeric. Some of the above examples of thermoplastic polymers 102 may be elastomeric or non-elastomeric depending on the exact composition of the polymer. For example, polyethylene, which is a copolymer of ethylene and propylene, may be elastomeric or non-elastomeric depending on the amount of propylene in the polymer.

[0047] Thermoplastic elastomers generally fall within one of six classes: styrenic block copolymers, thermoplastic polyolefin elastomers, thermoplastic vulcanizates (also called elastomeric alloys), thermoplastic polyurethanes, thermoplastic copolyesters, and thermoplastic polyamides (typically block copolymers containing polyamides). Examples of thermoplastic elastomers can be found in Handbook of Thermoplastic Elastomers, 2nd ed., BMW Alker and CP Rader, eds., Van Nostrand Reinhold, New York, 1988. Examples of thermoplastic elastomers include elastomeric polyamides, polyurethanes, copolymers containing polyether blocks and polyamide blocks (PEBA or polyether block amides), methyl methacrylate-butadiene-styrene (MBS) type core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymers, polybutadiene, polyisoprene, styrenic block copolymers, and polyacrylonitrile, silicones, and the like. The elastomeric styrenic block copolymer may include at least one block selected from the group consisting of isoprene, isobutylene, butylene, ethylene / butylene, ethylene-propylene, and ethylene-ethylene / propylene. More specific examples of elastomeric styrenic block copolymers include, but are not limited to, poly(styrene-ethylene / butylene), poly(styrene-ethylene / butylene-styrene), poly(styrene-ethylene / propylene), styrene-ethylene / propylene-styrene), poly(styrene-ethylene / propylene-styrene-ethylene-propylene), poly(styrene-butadiene-styrene), poly(styrene-butylene-butadiene-styrene), and the like, and any combination thereof.

[0048] Examples of polyamides include, but are not limited to, polycaproamide (nylon 6, polyamide 6, or PA6), poly(hexamethylene succinamide) (nylon 4,6, polyamide 4,6, or PA4,6), polyhexamethylene adipamide (nylon 6,6, polyamide 6,6, or PA6,6), polypentamethylene adipamide (nylon 5,6, polyamide 5,6, or PA5,6), polyhexamethylene sebacamide (nylon 6,10, polyamide 6,10, or PA6,10), polyundecaamide (nylon 11, polyamide 11, or PA11), polydodecaamide (nylon 12, polyamide 12, or PA12), and polyhexamethylene. Examples of suitable polyamides include ethylene terephthalamide (nylon 6T, polyamide 6T, or PA6T), nylon 10,10 (polyamide 10,10 or PA10,10), nylon 10,12 (polyamide 10,12 or PA10,12), nylon 10,14 (polyamide 10,14 or PA10,14), nylon 10,18 (polyamide 10,18 or PA10,18), nylon 6,18 (polyamide 6,18 or PA6,18), nylon 6,12 (polyamide 6,12 or PA6,12), nylon 6,14 (polyamide 6,14 or PA6,14), nylon 12,12 (polyamide 12,12 or PA12,12), and any combination thereof. Copolyamides may also be used. Examples of copolyamides include, but are not limited to, PA11 / 10,10, PA6 / 11, PA6,6 / 6, PA11 / 12, PA10,10 / 10,12, PA10,10 / 10,14, PA11 / 10,36, PA11 / 6,36, PA10,10 / 10,36, PA6T / 6,6, etc., and any combination thereof. A polyamide having a first number followed by a comma and a second number is a polyamide having a main chain carbon of the first number between the nitrogens of the portion that does not have a pendant =O, and a main chain carbon of the second number between two nitrogens of the portion that has a pendant =O. As a non-limiting example, nylon 6,10 is [NH-(CH2)6-NH-CO-(CH2)8-CO] n A polyamide followed by a number(s) backslash number(s) is a copolymer of the polyamide designated by the numbers before and after the backslash.

[0049] Examples of polyurethanes include, but are not limited to, polyether polyurethanes, polyester polyurethanes, mixed polyether and polyester polyurethanes, and the like, and any combination thereof. Examples of thermoplastic polyurethanes include, but are not limited to, poly[4,4'-methylenebis(phenylisocyanate)-alt-1,4-butanediol / di(propylene glycol) / polycaprolactone], ELASTOLLAN® 1190A (polyether polyurethane elastomer, available from BASF), ELASTOLLAN® 1190A10 (polyether polyurethane elastomer, available from BASF), and the like, and any combination thereof.

[0050] A compatibilizer may optionally be used to improve the efficiency and effectiveness of blending the thermoplastic polyester with one or more thermoplastic polymers. Examples of polymeric compatibilizers include, but are not limited to, PROPOLDER™ MPP2020 20 (polypropylene, available from Polygroup Inc.), PROPOLDER™ MPP2040 40 (polypropylene, available from Polygroup Inc.), NOVACOM™ HFS2100 (maleic anhydride functionalized high density polyethylene polymer, available from Polygroup Inc.), KEN-REACT™ CAPS™ L™ 12 / L (organometallic binder, available from Kenrich Petrochemicals), KEN-REACT™ CAPOW™ L™ 12 / H (organometallic binder, available from Kenrich Petrochemicals), KEN-REACT™ LICA™ 12 (organometallic binder, available from Kenrich Petrochemicals), KEN-REACT™ CAPS™ KPR™ 12 / LV (organometallic binder, available from Kenrich Petrochemicals), and KEN-REACT™ CAPS™ KPR™ 12 / LV (organometallic binder, available from Kenrich Petrochemicals). Petrochemicals), KEN-REACT™ CAPOW™ KPR™ 12 / H (organometallic binder, available from Kenrich Petrochemicals), KEN-REACT™ Titanate & Zirconate (organometallic binder, available from Kenrich Petrochemicals)Petrochemicals), VISTAMAXX™ (ethylene-propylene copolymer, available from ExxonMobil), SANTOPRENE™ (thermoplastic vulcanizates of ethylene-propylene-diene rubber and polypropylene, available from ExxonMobil), VISTALON™ (ethylene-propylene-diene rubber, available from ExxonMobil), EXACT™ (plastomers, available from ExxonMobil), EXXEL™ (poly ... OR™ (polymer resin, available from ExxonMobil), FUSABOND™ M603 (random ethylene copolymer, available from Dow), FUSABOND™ E226 (anhydride modified polyethylene, available from Dow), BYNEL™ 41E710 (coextrudable adhesive resin, available from Dow), SURLYN™ 1650 (ionomer resin, available from Dow), FUSABOND™ P353 (chemically modified polypropylene copolymer, available from Dow), , available from Dow), ELVALOY™ PTW (ethylene terpolymer, available from Dow), ELVALOY™ 3427AC (copolymer of ethylene and butyl acrylate, available from Dow), LOTADER™ AX8840 (ethylene acrylate-based terpolymer, available from Arkema), LOTADER™ 3210 (ethylene acrylate-based terpolymer, available from Arkema), LOTADER™ 3410 (ethylene acrylate-based terpolymer, available from Arkema), polymer, available from Arkema), LOTADER™ 3430 (ethylene acrylate based terpolymer, available from Arkema), LOTADER™ 4700 (ethylene acrylate based terpolymer, available from Arkema), LOTADER™ AX8900 (ethylene acrylate based terpolymer, available from Arkema), LOTADER™ 4720 (ethylene acrylate based terpolymer, available from Arkema), BAXXODUR™ EC 301 (amine for epoxies, available from BASF), BAXXODUR™ EC 311 (amine for epoxies, available from BASF), BAXXODUR™ EC303 (amine for epoxies, available from BASF), BAXXODUR™ EC 280 (amine for epoxies, available from BASF), BAXXODUR™ EC 201 (amine for epoxies, available from BASF), BAXXODUR™ EC 130 (amine for epoxies, available from BASF), BAXXODUR™ EC 110 (amine for epoxies, available from BASF), styrene, polypropylene, polyamide, polycarbonate, EASTMAN™ G-3003 (maleic anhydride grafted polypropylene, available from Eastman), RETAIN™ (polymer modifier, available from Dow), AMPLIFY TY™ (maleic anhydride grafted polymer, available from Dow), INTUNE™ (olefin block copolymer, available from Dow), and any combination thereof.

[0051] Thermoplastic polymer 102 may have a melting point or softening temperature of about 50°C to about 450°C (or about 50°C to about 125°C, or about 100°C to about 175°C, or about 150°C to about 280°C, or about 200°C to about 350°C, or about 300°C to about 450°C).

[0052] Thermoplastic polymer 102 may have a glass transition temperature (ASTM E1356-08(2014) using 10°C / min heating and cooling rates) of about -50°C to about 400°C (or about -50°C to about 0°C, or about -25°C to about 50°C, or about 0°C to about 150°C, or about 100°C to about 250°C, or about 150°C to about 300°C, or about 200°C to about 400°C).

[0053] The thermoplastic polymer 102 may optionally include an additive. Typically, the additive is present prior to adding the thermoplastic polymer 102 to the mixture 110. Thus, in the thermoplastic polymer melt droplets and the resulting thermoplastic polymer particles, the additive is dispersed throughout the thermoplastic polymer. Accordingly, for clarity, this additive is referred to herein as an "internal additive." The internal additive may be blended with the thermoplastic polymer immediately prior to pre-forming the mixture 110 or well.

[0054] When describing amounts of components in compositions described herein (e.g., mixture 110 and thermoplastic polymer particles 122), the weight percentages are based on the thermoplastic polymer 102 without the internal additive. For example, a composition that includes 1% by weight of emulsion stabilizer based on the weight of 100 g of thermoplastic polymer 102 that includes 10% by weight of internal additive and 90% by weight of thermoplastic polymer is a composition that includes 0.9 g of emulsion stabilizer, 90 g of thermoplastic polymer, and 10 g of internal additive.

[0055] The internal additive may be present in the thermoplastic polymer 102 at about 0.1% to about 60% by weight (or about 0.1% to about 5%, or about 1% to about 10%, or about 5% to about 20%, or about 10% to about 30%, or about 25% to about 50%, or about 40% to about 60% by weight) of the thermoplastic polymer 102. For example, the thermoplastic polymer 102 may include about 70% to about 85% by weight of the thermoplastic polymer and about 15% to about 30% by weight of the internal additive, such as glass fiber or carbon fiber.

[0056] Examples of internal additives include, but are not limited to, fillers, reinforcing agents, pigments, pH adjusters, and the like, and combinations thereof. Examples of fillers include, but are not limited to, glass fibers, glass particles, mineral fibers, carbon fibers, oxide particles (e.g., titanium dioxide and zirconium dioxide), metal particles (e.g., aluminum powder), and the like, and any combinations thereof. Examples of pigments include, but are not limited to, organic pigments, inorganic pigments, carbon black, and the like, and any combinations thereof.

[0057] The thermoplastic polymer 102 may be present in the mixture 110 at about 5% to about 60% by weight (or about 5% to about 25% by weight, or about 10% to about 30% by weight, or about 20% to about 45% by weight, or about 25% to about 50% by weight, or about 40% to about 60% by weight) of the combined thermoplastic polymer 102 and dispersion medium 104.

[0058] A suitable dispersion medium 104 has a viscosity at 25° C. of about 1,000 cSt to about 150,000 cSt (or about 1,000 cSt to about 60,000 cSt, or about 40,000 cSt to about 100,000 cSt, or about 75,000 cSt to about 150,000 cSt).

[0059] Examples of the dispersion medium 104 include, but are not limited to, silicone oils, fluorinated silicone oils, perfluorinated silicone oils, polyethylene glycols, alkyl terminated polyethylene glycols (e.g., C1-C4 terminal alkyl groups such as tetraethylene glycol dimethyl ether (TDG)), paraffin, liquid petrolatum, mink oil, turtle oil, soybean oil, perhydrosqualene, sweet almond oil, calophyllum oil, palm oil, pearl oil, grapeseed oil, sesame oil, corn oil, rapeseed oil, sunflower oil, cottonseed oil, apricot oil, castor oil, avocado oil, jojoba oil, olive oil, cereal germ oil, esters of lanolin acid, esters of oleic acid, esters of lauric acid, esters of stearic acid, fatty esters, higher fatty acids, fatty alcohols, fatty acid modified polysiloxanes, fatty alcohol modified polysiloxanes, polyoxyalkylene modified polysiloxanes, and the like, and any combination thereof. Examples of silicone oils include, but are not limited to, polydimethylsiloxane, methylphenylpolysiloxane, alkyl-modified polydimethylsiloxane, alkyl-modified methylphenylpolysiloxane, amino-modified polydimethylsiloxane, amino-modified methylphenylpolysiloxane, fluorine-modified polydimethylsiloxane, fluorine-modified methylphenylpolysiloxane, polyether-modified polydimethylsiloxane, polyether-modified methylphenylpolysiloxane, and the like, and any combination thereof. The dispersion medium 104 may have one or more phases. For example, a fatty acid-modified polysiloxane and an aliphatic alcohol-modified polysiloxane (preferably with similar chain lengths as the fatty acid and the aliphatic alcohol) may form a single-phase dispersion medium 104. In another example, a dispersion medium 104 including a silicone oil and an alkyl-terminated polyethylene glycol may form a two-phase dispersion medium 104.

[0060] The dispersion medium 104 may be present in the mixture 110 at about 40% to about 95% by weight (or about 75% to about 95% by weight, or about 70% to about 90% by weight, or about 55% to about 80% by weight, or about 50% to about 75% by weight, or about 40% to about 60% by weight) of the combined thermoplastic polymer 102 and dispersion medium 104.

[0061] In some cases, the dispersion medium 104 has a density of about 0.6 g / cm 3 ~Approx. 1.5g / cm 3 and the thermoplastic polymer 102 may have a density of about 0.7 g / cm 3 ~Approx. 1.7g / cm 3 and the thermoplastic polymer has a density similar to, lower than, or higher than the density of the dispersion medium.

[0062] Emulsion stabilizers used in the methods and compositions of the present disclosure may include nanoparticles (e.g., oxide nanoparticles, carbon black, polymeric nanoparticles, and combinations thereof), surfactants, and the like, and any combinations thereof.

[0063] The oxide nanoparticles may be metal oxide nanoparticles, non-metal oxide nanoparticles, or mixtures thereof. Examples of oxide nanoparticles include, but are not limited to, silica, titania, zirconia, alumina, iron oxide, copper oxide, tin oxide, boron oxide, cerium oxide, thallium oxide, tungsten oxide, and the like, and any combination thereof. Mixed metal oxides and / or non-metal oxides, such as aluminosilicates, borosilicates, and aluminoborosilicates, are also included in the term metal oxide. The oxide nanoparticles may be hydrophilic or hydrophobic and may be natural particles or the result of surface treatment of the particles. For example, silica nanoparticles with hydrophobic surface treatments, such as dimethylsilyl, trimethylsilyl, and the like, may be used in the methods and compositions of the present disclosure. In addition, silicas with functional surface treatments, such as methacrylate functional groups, may be used in the methods and compositions of the present disclosure. Non-functionalized oxide nanoparticles may be suitable for use as well.

[0064] Commercially available examples of silica nanoparticles include, but are not limited to, AEROSIL® available from Evonik (e.g., AEROSIL® R812S (with hydrophobically modified surface and 260±30 m 2 / g BET surface area), AEROSIL® RX50 (hydrophobically modified surface and 35±10m 2 / g BET surface area), AEROSIL® 380 (hydrophobically modified surface and 380±30m 2 / g) silica nanoparticles), and any combination thereof.

[0065] Carbon black is another type of nanoparticle that may be present as an emulsion stabilizer in the compositions and methods disclosed herein. Various grades of carbon black are familiar to those skilled in the art, any of which may be used herein. Other nanoparticles capable of absorbing infrared radiation may be used as well.

[0066] Polymer nanoparticles are another type of nanoparticle that may be present as an emulsion stabilizer in the present disclosure.Suitable polymer nanoparticles may include one or more polymers that are thermosetting and / or crosslinked so that they do not melt when processed by melt emulsification according to the present disclosure.High molecular weight thermoplastic polymers with high melting or decomposition points may also comprise suitable polymer nanoparticle emulsion stabilizers.

[0067] The nanoparticles can have an average diameter (D50 based on volume) of about 1 nm to about 500 nm (or about 10 nm to about 150 nm, or about 25 nm to about 100 nm, or about 100 nm to about 250 nm, or about 250 nm to about 500 nm).

[0068] Nanoparticles are about 10m 2 / g~about 500m 2 / g (or about 10m 2 / g~about 150m 2 / g, or about 25m 2 / g~about 100m 2 / g, or about 100m 2 / g ~ approx. 250m 2 / g, or 250m 2 / g~about 500m 2 / g).

[0069] The nanoparticles may be included in the mixture 110 at a concentration of about 0.01% to about 10% by weight (or about 0.01% to about 1% by weight, or about 0.1% to about 3% by weight, or about 1% to about 5% by weight, or about 5% to about 10% by weight), based on the weight of the thermoplastic polymer 102.

[0070] The surfactant may be anionic, cationic, nonionic, or zwitterionic. Examples of surfactants include, but are not limited to, sodium dodecyl sulfate, sorbitan oleate, poly[dimethylsiloxane-co-[[3-(2-(2-hydroxyethoxy)ethoxy)propylmethylsiloxane], docusate sodium (sodium 1,4-bis(2-ethylhexoxy)-1,4-dioxobutane-2-sulfonate), and the like, and any combination thereof. Commercially available examples of surfactants include, but are not limited to, CALFAX® DB-45 (sodium dodecyl diphenyl oxide disulfonate, available from Pilot Chemicals), SPAN® 80 (sorbitan maleate nonionic surfactant), MERPOL® surfactants (available from Stepan Company), TERGITOL™ TMN-6 (water soluble nonionic surfactant, available from DOW), TRITON® X-100 (octylphenol ethoxylate, available from SigmaAldrich), IGEPAL® CA-520 (polyoxyethylene (5) isooctylphenyl ether, available from SigmaAldrich), BRIJ® S10 (polyethylene glycol octadecyl ether, available from SigmaAldrich), and the like, and any combination thereof.

[0071] The surfactant may be included in mixture 110 at a concentration of about 0.01% to about 10% by weight (or about 0.01% to about 1% by weight, or about 0.5% to about 2% by weight, or about 1% to about 3% by weight, or about 2% to about 5% by weight, or about 5% to about 10% by weight), based on the weight of polyamide 102. Alternatively, mixture 110 may be free of (or absent from) a surfactant.

[0072] The weight ratio of nanoparticles to surfactant can be from about 1:10 to about 10:1 (or from about 1:10 to about 1:1, or from about 1:5 to about 5:1, or from about 1:1 to about 10:1).

[0073] As mentioned above, the components 102, 104, and 106 may be added in any order and may include mixing and / or heating during the process 108 including the components 102, 104, and 106. For example, the emulsion stabilizer 106 may first be dispersed in the dispersion medium 104 prior to adding the thermoplastic polymer 102, optionally with heating of the dispersion. In another non-limiting example, the thermoplastic polymer 102 may be heated to produce a polymer melt to which the dispersion medium 104 and the emulsion stabilizer 106 are added together or in any order. In yet another non-limiting example, the thermoplastic polymer 102 and the dispersion medium 104 may be mixed at a temperature above the melting point or softening temperature of the thermoplastic polymer 102 and at a shear rate sufficient to disperse the thermoplastic polymer melt in the dispersion medium 104. The emulsion stabilizer 106 may then be added to form the mixture 110 and maintained at suitable process conditions for a set period of time.

[0074] Combining 108 the components 102, 104, and 106 in any combination may occur in a mixing device and / or another suitable vessel used for process 112. As a non-limiting example, the thermoplastic polymer 102 may be heated to a temperature above the melting point or softening temperature of the thermoplastic polymer 102 in the mixing device used for process 112, and the emulsion stabilizer 106 may be dispersed in the dispersion medium 104 in a separate vessel. The dispersion may then be added to a melt of the thermoplastic polymer 102 in the mixing device used for process 112.

[0075] The mixing equipment used in process 112 to produce the molten emulsion 114 should be capable of maintaining the molten emulsion 114 at a temperature above the melting point or softening temperature of the thermoplastic polymer 102 and applying a shear rate sufficient to disperse the polymer melt as droplets in the dispersion medium 104.

[0076] Examples of mixing equipment used in process 112 to produce molten emulsion 114 include, but are not limited to, extruders (e.g., continuous extruders, batch extruders, etc.), stirred reactors, blenders, reactors with in-line homogenizer systems, etc., and equipment derived therefrom.

[0077] Processing 112 at suitable process conditions (eg, temperature, shear rate, etc.) for a set period of time and forming a molten emulsion 114.

[0078] The temperature of process 112 and formation of molten emulsion 114 should be a temperature above the melting point or softening temperature of thermoplastic polymer 102 and below the decomposition temperature of any of components 102, 104, and 106 in mixture 110. For example, the temperature of process 112 and formation of molten emulsion 114 may be about 1° C. to about 50° C. (or about 1° C. to about 25° C., or about 5° C. to about 30° C., or about 20° C. to about 50° C.) above the melting point or softening temperature of thermoplastic polymer 102, provided that the temperature of process 112 and formation of molten emulsion 114 is below the decomposition temperature of any of components 102, 104, and 106 in mixture 110.

[0079] The shear rate of process 112 and formation of melt emulsion 114 should be high enough to disperse the polymer melt as droplets in dispersion medium 104. The droplets should include droplets having a diameter of about 1000 μm or less (or from about 1 μm to about 1000 μm, or from about 1 μm to about 50 μm, or from about 10 μm to about 100 μm, or from about 10 μm to about 250 μm, or from about 50 μm to about 500 μm, or from about 250 μm to about 750 μm, or from about 500 μm to about 1000 μm).

[0080] The time for maintaining the temperature and shear rate for process 112 and forming molten emulsion 114 may be from 10 seconds to 18 hours or more (or from 10 seconds to 30 minutes, or from 5 minutes to 1 hour, or from 15 minutes to 2 hours, or from 1 hour to 6 hours, or from 3 hours to 18 hours). Without being bound by theory, it is believed that a steady state in droplet size is reached at which point process 112 may be stopped. That time may depend on, among other things, the temperature, the shear rate, the composition of the thermoplastic polymer 102, the composition of the dispersion medium 104, and the composition of the emulsion stabilizer 106.

[0081] The molten emulsion 114 may then be cooled (116). The cooling 116 may be slow (e.g., allowing the molten emulsion to cool under ambient conditions) to fast (e.g., rapid cooling). For example, the cooling rate may range from about 10° C. / hour to about 100° C. / second to nearly instantaneous with rapid cooling (e.g., dry ice) (or from about 10° C. / hour to about 60° C. / hour, or from about 0.5° C. / minute to about 20° C. / minute, or from about 1° C. / minute to about 5° C. / minute, or from about 10° C. / minute to about 60° C. / minute, or from about 0.5° C. / second to about 10° C. / second, or from about 10° C. / second to about 100° C. / second).

[0082] During cooling, little or no shear force may be applied to the molten emulsion 114. In some cases, the shear force applied during heating may be applied during cooling.

[0083] The cooled mixture 118 resulting from cooling 116 of the molten emulsion 114 contains solidified thermoplastic polymer particles 122 (or simply thermoplastic polymer particles) and other components 124 (e.g., the dispersion medium 104, excess emulsion stabilizer 106, etc.). The thermoplastic polymer particles may be dispersed in the dispersion medium or may settle in the dispersion medium.

[0084] The cooled mixture 118 may then be processed (120) into separate thermoplastic polymer particles 122 (or simply thermoplastic polymer particles 122) from other components 124. Suitable processing includes, but is not limited to, washing, filtering, centrifuging, decanting, the like, and any combination thereof.

[0085] The solvent used to wash the thermoplastic polymer particles 122 should generally be (a) miscible with the carrier fluid 104 and (b) non-reactive (e.g., non-swelling and non-melting) with the thermoplastic polymer 102. The choice of solvent will depend, among other things, on the composition of the carrier fluid and the composition of the thermoplastic polymer 102.

[0086] Examples of solvents include, but are not limited to, hydrocarbon solvents (e.g., pentane, hexane, heptane, octane, cyclohexane, cyclopentane, decane, dodecane, tridecane, and tetradecane), aromatic hydrocarbon solvents (e.g., benzene, toluene, xylene, 2-methylnaphthalene, and cresol), ether solvents (e.g., diethyl ether, tetrahydrofuran, diisopropyl ether, and dioxane), ketone solvents (e.g., acetone and methyl ethyl ketone), alcohol solvents (e.g., methanol, ethanol, isopropanol, and n-propanol), ester solvents (e.g., ethyl acetate, methyl acetate, butyl acetate, butyl propionate, and butyl butyrate), halogenated solvents (e.g., chloroform, bromoform, 1,2-dichloromethane, 1,2-dichloroethane, carbon tetrachloride, chlorobenzene, and hexafluoroisopropanol), water, and the like, and any combination thereof.

[0087] The solvent may be removed from the thermoplastic polymer particles 122 by drying using a suitable method such as air drying, heat drying, vacuum drying, freeze drying, or a hybrid thereof. Heating may be preferably performed at a temperature below the glass transition point of the thermoplastic polymer (e.g., about 50° C. to about 150° C.).

[0088] The thermoplastic polymer particles 122 after separation from other components 124 may, if desired, be further classified to produce purified thermoplastic polymer particles 128. For example, to narrow the particle size distribution (or reduce the diameter span), the thermoplastic polymer particles 122 may be passed through a sieve having a pore size of about 10 μm to about 250 μm (or about 10 μm to about 100 μm, or about 50 μm to about 200 μm, or about 150 μm to about 250 μm).

[0089] In another exemplary purification technique, the thermoplastic polymer particles 122 may be washed with water to remove the surfactant while retaining substantially all of the nanoparticles associated with the surface of the thermoplastic polymer particles 122. In yet another exemplary purification technique, the thermoplastic polymer particles 122 may be blended with additives to obtain a desired end product. For clarity, such additives are referred to herein as "external additives" because they are blended with the thermoplastic particles 122 or other particles resulting from the methods described herein after the particles have solidified. Examples of external additives include flow aids, other polymer particles, fillers, and the like, and any combination thereof.

[0090] In some cases, the surfactant used in the production of the thermoplastic polymer particles 122 may be unnecessary in downstream applications. Accordingly, yet another exemplary purification technique may include at least substantially removing the surfactant from the thermoplastic polymer particles 122 (e.g., by washing and / or pyrolysis).

[0091] The thermoplastic polymer particles 122 and / or the refined thermoplastic polymer particles 128 (referred to as particles 122 / 128) may be characterized by composition, physical structure, and the like.

[0092] As mentioned above, the emulsion stabilizer is at the interface between the polymer melt and the dispersion medium. As a result, when the mixture cools, the emulsion stabilizer remains at or near that interface. Thus, the structure of the particles 122 / 128 generally includes (a) the emulsion stabilizer dispersed on the outer surface of the particles 122 / 128, and / or (b) the emulsion stabilizer embedded in the outer portion (e.g., the outer 1% by volume) of the particles 122 / 128.

[0093] Additionally, if voids are formed within the polymer melt droplets, the emulsion stabilizer 106 should generally be present (and / or embedded) at the interface between the interior of the void and the thermoplastic polymer. The voids generally do not contain thermoplastic polymer. Rather, the voids may contain, for example, a dispersion medium, air, or may be empty. The particles 122 / 128 may contain about 5% or less (or about 0.001% to about 5% by weight, or about 0.001% to about 0.1% by weight, or about 0.01% to about 0.5% by weight, or about 0.1% to about 2% by weight, or about 1% to about 5% by weight) of the dispersion medium by weight of the particles 122 / 128.

[0094] The thermoplastic polymer 102 may be present in the particles 122 / 128 at about 90% to about 99.5% by weight (or about 90% to about 95% by weight, or about 92% to about 97% by weight, or about 95% to about 99.5% by weight) of the particles 122 / 128.

[0095] Emulsion stabilizer 106 may be present in particle 122 / 128 at about 10% or less by weight of particle 122 / 128 (or from about 0.01% to about 10% by weight, or from about 0.01% to about 1% by weight, or from about 0.5% to about 5% by weight, or from about 3% to about 7% by weight, or from about 5% to about 10% by weight). When purified to at least substantially remove surfactant or another emulsion stabilizer, emulsion stabilizer 106 may be present in particle 128 at less than 0.01% by weight (or from 0% to about 0.01% by weight, or from 0% to 0.001% by weight).

[0096] In forming the thermoplastic microparticles according to the disclosure herein, at least a portion of the nanoparticles, such as silica nanoparticles, may be disposed as a coating on the outer surface of the thermoplastic microparticle. At least a portion of the surfactant, if used, may be associated with the outer surface as well. The coating may be substantially uniformly disposed on the outer surface. As used herein with respect to the coating, the term "substantially uniform" refers to a uniform coating thickness at the surface locations covered by the coating composition (e.g., nanoparticles and / or surfactant), particularly the entire outer surface. The emulsion stabilizer 106 may form a coating that covers at least 5% (or from about 5% to about 100%, or from about 5% to about 25%, or from about 20% to about 50%, or from about 40% to about 70%, or from about 50% to about 80%, or from about 60% to about 90%, or from about 70% to about 100%) of the surface area of ​​the particle 122 / 128. When purified to at least substantially remove surfactant or another emulsion stabilizer, emulsion stabilizer 106 may be present in particle 128 on less than 25% (or from 0% to about 25%, or from about 0.1% to about 5%, or from about 0.1% to about 1%, or from about 1% to about 5%, or from about 1% to about 10%, or from about 5% to about 15%, or from about 10% to about 25%) of the surface area of ​​particle 128. The coverage of emulsion stabilizer 106 on the outer surface of particle 122 / 128 may be determined using image analysis of SEM micrographs. The emulsion stabilizer 106 may form a coating that covers at least 5% (or from about 5% to about 100%, or from about 5% to about 25%, or from about 20% to about 50%, or from about 40% to about 70%, or from about 50% to about 80%, or from about 60% to about 90%, or from about 70% to about 100%) of the surface area of ​​the particle 122 / 128. When purified to at least substantially remove surfactant or another emulsion stabilizer, the emulsion stabilizer 106 may be present in the particle 128 on less than 25% (or from 0% to about 25%, or from about 0.1% to about 5%, or from about 0.1% to about 1%, or from about 1% to about 5%, or from about 1% to about 10%, or from about 5% to about 15%, or from about 10% to about 25%) of the surface area of ​​the particle 128. The coverage of emulsion stabilizer 106 on the outer surface of particles 122 / 128 can be determined using image analysis of SEM micrographs.

[0097] Particles 122 / 128 may have a D10 of about 0.1 μm to about 125 μm (or about 0.1 μm to about 5 μm, about 1 μm to about 10 μm, about 5 μm to about 30 μm, or about 1 μm to about 25 μm, or about 25 μm to about 75 μm, or about 50 μm to about 85 μm, or about 75 μm to about 125 μm), a D50 of about 0.5 μm to about 200 μm (or about 0.5 μm to about 10 μm, or about 5 μm to about 50 μm, or about 30 μm to about 100 μm, or about 30 μm to about 70 μm, or about 25 μm to about 50 μm, or about 50 μm to about 100 μm, or about 75 μm to about 150 μm, or about 100 μm to about 200 μm), and a D90 of about 3 μm to about 300 μm (or about 3 μm to about 15 μm, or about 10 μm to about 50 μm, or about 25 μm to about 75 μm, or about 70 μm to about 200 μm, or about 60 μm to about 150 μm, or about 150 μm to about 300 μm), with D10 < D50 < D90. Particles 122 / 128 may also have a diameter span of about 0.2 to about 10 (or about 0.2 to about 0.5, or about 0.4 to about 0.8, or about 0.5 to about 1.0, or about 1 to about 3, or about 2 to about 5, or about 5 to about 10). Without limitation, a diameter span value of 1.0 or greater is considered wide, and a diameter span value of 0.75 or less is considered narrow. Without limitation, a diameter span value of 1.0 or greater is considered wide, and a diameter span value of 0.75 or less is considered narrow.

[0098] In a first non - limiting example, particles 122 / 128 may have a D10 of about 0.1 μm to about 10 μm, a D50 of about 0.5 μm to about 25 μm, and a D90 of about 3 μm to about 50 μm, with D10 < D50 < D90. The particles 122 / 128 may have a diameter span of about 0.2 to about 2.

[0099] In a second non - limiting example, particles 122 / 128 may have a D10 of about 5 μm to about 30 μm, a D50 of about 30 μm to about 70 μm, and a D90 of about 70 μm to about 120 μm, with D10 < D50 < D90. The particles 122 / 128 may have a diameter span of about 1.0 to about 2.5.

[0100] In a third non-limiting example, the particles 122 / 128 can have a D10 of about 25 μm to about 60 μm, a D50 of about 60 μm to about 110 μm, and a D90 of about 110 μm to about 175 μm, with D10 < D50 < D90. The particles 122 / 128 can have a diameter span of about 0.6 to about 1.5.

[0101] In a fourth non-limiting example, the particles 122 / 128 can have a D10 of about 75 μm to about 125 μm, a D50 of about 100 μm to about 200 μm, and a D90 of about 125 μm to about 300 μm, with D10 < D50 < D90. The particles 122 / 128 can have a diameter span of about 0.2 to about 1.2.

[0102] In a fifth non-limiting example, the particles 122 / 128 can have a D10 of about 1 μm to about 50 μm (or about 5 μm to about 30 μm, or about 1 μm to about 25 μm, or about 25 μm to about 50 μm), a D50 of about 25 μm to about 100 μm (or about 30 μm to about 100 μm, or about 30 μm to about 70 μm, or about 25 μm to about 50 μm, or about 50 μm to about 100 μm), and a D90 of about 60 μm to about 300 μm (or about 70 μm to about 200 μm, or about 60 μm to about 150 μm, or about 150 μm to about 300 μm), with D10 < D50 < D90. The particles 122 / 128 can also have a diameter span of about 0.4 to about 3 (or about 0.6 to about 2, or about 0.4 to about 1.5, or about 1 to about 3).

[0103] The particles 122 / 128 can have a circularity of about 0.7 or more (or about 0.7 to about 0.95, or about 0.9 to about 1.0, or about 0.93 to about 0.99, or about 0.95 to about 0.99, or about 0.97 to about 0.99, or about 0.98 to 1.0).

[0104] The particles 122 / 128 can have an angle of repose of about 20° to about 45° (or about 25° to about 35°, or about 30° to about 40°, or about 35° to about 45°).

[0105] Particles 122 / 128 can have a Hausner ratio of about 1.0 to about 1.5 (or about 1.0 to about 1.2, or about 1.1 to about 1.3, or about 1.2 to about 1.35, or about 1.3 to about 1.5).

[0106] Particle 122 / 128 is approximately 0.3 g / cm 3 ~about 0.8g / cm 3 (or about 0.3 g / cm 3 ~about 0.6g / cm 3 , or about 0.4 g / cm 3 ~about 0.7g / cm 3 , or about 0.5 g / cm 3 ~about 0.6g / cm 3 , or about 0.5 g / cm 3 ~about 0.8g / cm 3 ) bulk density.

[0107] Depending on the temperature and shear rate of the process 112, and the composition and relative concentrations of the components 102, 104, and 106, different shapes of the structures that make up the particles 122 / 128 have been observed. Typically, the particles 122 / 128 include substantially spherical particles (having a circularity of about 0.97 or greater). However, other structures have been observed in the particles 122 / 128, including disk structures and elongated structures. Thus, the particles 122 / 128 may include one or more of: (a) substantially spherical particles having a circularity of 0.97 or greater; (b) disk structures having an aspect ratio of about 2 to about 10; and (c) elongated structures having an aspect ratio of 10 or greater. Each of the (a), (b), and (c) structures has an emulsion stabilizer dispersed on the outer surfaces of the (a), (b), and (c) structures, and / or an emulsion stabilizer embedded in the outer portions of the (a), (b), and (c) structures. At least some of the (a), (b), and (c) structures may be aggregated, for example, the elongated structures of (c) may be located on the surface of a substantially spherical particle of (a).

[0108] Particles 122 / 128 may have a sintering time within 10° C., preferably within 5° C., of the sintering time of thermoplastic polymer 102 (which includes one or more PP-polyamides and optionally one or more other thermoplastic polymers).

[0109] Applications of Thermoplastic Polymer Particles The thermoplastic polymer particles described herein can be utilized in 3D printing processes, particularly those that use selective laser sintering to promote particle consolidation.The thermoplastic polymer particles of the present disclosure can exhibit advantageous properties over polymer particulates with irregular shapes or broader particle distributions, such as those commercially available.In a non-limiting example, the thermoplastic polymer particles of the present disclosure can be consolidated at lower laser power, resulting in a reduced degree of void formation within the object produced by 3D printing.

[0110] The 3D printing process of the present disclosure may include depositing the thermoplastic polymer particles of the present disclosure onto a surface of a particular shape, and after deposition, heating at least a portion of the thermoplastic polymer particles to promote their consolidation to form a consolidated body (object) such that the consolidated body has a porosity of about 1% or less after consolidation. For example, the heating and consolidation of the thermoplastic polymer particles may be performed in a laser-based 3D printing device such that the heating and consolidation is performed by selective laser sintering.

[0111] Any of the thermoplastic polymer particles disclosed herein can be formulated into a composition suitable for 3D printing. The selection of the composition and type of elastomeric particles can be based on a variety of factors, including, but not limited to, the laser power used for selective laser sintering, the type of object being produced, and the intended use conditions of the object.

[0112] Examples of objects that can be 3D printed using the thermoplastic polymer particles of the present disclosure include, but are not limited to, containers (e.g., food, beverages, cosmetics, personal care compositions, pharmaceuticals, etc.), shoe soles, toys, furniture parts and home decor items, plastic gears, screws, nuts, bolts, cable ties, automotive parts, medical items, prostheses, orthopedic implants, aerospace / aviation related parts, generation of artifacts to aid in education and learning, 3D anatomical models to aid in surgery, robots, biomedical devices (prosthetics), home appliances, dental tools, electronic devices, sporting goods, and the like.

[0113] Other applications of the thermoplastic particulates of the present disclosure may include, but are not limited to, use as fillers in paints and powder coatings, inkjet materials, electrophotographic toners, etc. In some cases, the thermoplastic particulates may have other preferred characteristics, such as diameter and span, that are useful in the other applications listed above.

[0114] Non-Limiting Exemplary Embodiments A first non-limiting embodiment of the present disclosure is a composition comprising particles comprising a thermoplastic polymer (e.g., a thermoplastic elastomer) and an emulsion stabilizer (e.g., nanoparticles and / or surfactant) associated with an outer surface of the particle. The first non-limiting embodiment may include one or more of the following: Element 1: The emulsion stabilizer comprises nanoparticles, at least some of the nanoparticles are embedded in the outer surface of the particle; Element 2: The thermoplastic polymer is present at 90% to 99.5% by weight of the particle; Element 3: At least some of the particles have voids at the void / thermoplastic polymer interface that include the emulsion stabilizer; Element 4: Element 3, where the emulsion stabilizer comprises nanoparticles, the nanoparticles are embedded at the void / thermoplastic polymer interface; Element 5: Element 3, where the voids include a dispersion medium having a viscosity of 1,000 cSt to 150,000 cSt at 25° C.; Element 6: The particle further comprises elongated structures on the surface of the particle, where the elongated structures include a thermoplastic polymer, and the emulsion stabilizer is elongated. is associated with the outer surface of the structure;Element 7: the emulsion stabilizer forms a coating that covers less than 5% of the surface of the particle;Element 8: the emulsion stabilizer forms a coating that covers at least 5% of the surface of the particle;Element 9: the emulsion stabilizer forms a coating that covers at least 25% of the surface of the particle;Element 10: the emulsion stabilizer forms a coating that covers at least 50% of the surface of the particle;Element 11: the particle further comprises a dispersion medium having a viscosity of 1,000 cSt to 150,000 cSt at 25°C;Element 12: the dispersion medium is present at about 5% by weight or less of the particle;Element 13: the nanoparticles have an average diameter of 1 nm to 500 nm;Element 14: the nanoparticles are at a viscosity of 10 μm to 500 μm; 2 / g~500m 2having a BET surface area of / g; Element 15: The thermoplastic polymer is selected from the group consisting of polyamide, polyurethane, polyethylene, polypropylene, polyacetal, polycarbonate, polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polytrimethylene terephthalate (PTT), polyhexamethylene terephthalate, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyester (e.g., polylactic acid), polyether, polyethersulfone, polyetheretherketone, polyacrylate, polymethacrylate, polyimide, acrylonitrile butadiene styrene (ABS), polyphenylene sulfide, vinyl polymer, polyarylene ether, polyarylene sulfide, polysulfone, polyether ketone, polyamideimide, polyetherimide, polyether ester, polyether block and polyamide block (PEBA or polyether block amide) copolymers, grafted or ungrafted thermoplastic polyolefins, functionalized or non-functionalized ethylene / vinyl monomer polymers, functionalized or non-functionalized ethylene / alkyl (meth)acrylate, functionalized or non-functionalized (meth)acrylic acid polymers, functionalized or non-functionalized ethylene / vinyl monomer / alkyl (meth)acrylate terpolymers, ethylene / vinyl monomer / carbonyl terpolymers, ethylene / alkyl (meth)acrylate / carbonyl terpolymers, methyl methacrylate-butadiene-styrene (MBS) type core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymers, chlorinated or chlorosulfonated polyethylene, polyvinylidene fluoride (PVDF), phenolic resin, poly(ethylene / vinyl acetate), polybutadiene, polyisoprene, styrenic block copolymers, polyacrylonitrile, silicone, and any combination thereof; Element 16: The melting point or softening temperature of the thermoplastic polymer is from 50 °C to 450 °C; Element 17: The particles have a D10 of about 0.5 μm to about 125 μm, a D50 of about 1 μm to about 200 μm, and a D90 of about 70 μm to about 300 μm, with D10 < D50 < D90; Element 18: The particles are about 0.Having a diameter span of from 2 to about 10; Element 19: The particles have a D10 of from about 5 μm to about 30 μm, a D50 of from about 30 μm to about 70 μm, and a D90 of from about 70 μm to about 120 μm, and D10 < D50 < D90; Element 20: Element 19, and the particles have a diameter span of from about 1.0 to about 2.5; Element 21: The particles have a D10 of from about 25 μm to about 60 μm, a D50 of from about 60 μm to about 110 μm, and a D90 of from about 110 μm to about 175 μm, and D10 < D50 < D90; Element 22: Element 21, and the particles have a diameter span of from about 0.6 to about 1.5; Element 23: The particles have a D10 of from about 75 μm to about 125 μm, a D50 of from about 100 μm to about 200 μm, and a D90 of from about 125 μm to about 300 μm, and D10 < D50 < D90, Element 24: Element 23, and the solidified particles have a diameter span of from about 0.2 to about 1; Element 25: The particles have a circularity of from about 0.90 to about 1.0; and Element 26: The particles have a Hausner ratio of from about 1.0 to about 1.5. Examples of combinations include, but are not limited to, a combination of Element 1 and one or more of Elements 2 to 26, a combination of Element 3 (optionally in combination with Element 4 and / or Element 5) and one or more of Elements 2 and 4 to 26, and a combination of two or more of Elements 1 to 15.

[0115] A second non-limiting embodiment of the present disclosure is a method comprising: mixing a mixture comprising a thermoplastic polymer, a dispersion medium immiscible with the thermoplastic polymer (e.g., a thermoplastic elastomer), and an emulsion stabilizer (e.g., nanoparticles and / or surfactant) at a temperature above the melting point or softening temperature of the thermoplastic polymer and at a shear rate high enough to disperse the thermoplastic polymer in the dispersion medium; cooling the mixture below the melting point or softening temperature of the thermoplastic polymer to form solidified particles comprising the thermoplastic polymer and the emulsion stabilizer associated with an outer surface of the solidified particles; and separating the solidified particles from the dispersion medium.A first non-limiting embodiment can include one or more of the following: element 1; element 2; element 3; element 4; element 5; element 6; element 7; element 8; element 9; element 10; element 11; element 12; element 13; element 14; element 15; element 16; element 17; element 18; element 19; element 20; element 21; element 22; element 23; element 24; element 25; element 26; element 27: the thermoplastic polymer is present in the mixture at 5% to 60% by weight of the mixture; element 28: the emulsion stabilizer is 0.05% by weight of the thermoplastic polymer. Element 29: The dispersion medium is selected from the group consisting of silicone oil, fluorinated silicone oil, perfluorinated silicone oil, polyethylene glycol, alkyl terminated polyethylene glycol, paraffin, liquid petrolatum, mink oil, turtle oil, soybean oil, perhydrosqualene, sweet almond oil, calophyllum oil, palm oil, pearl oil, grapeseed oil, sesame oil, corn oil, rapeseed oil, sunflower oil, cottonseed oil, apricot oil. , castor oil, avocado oil, jojoba oil, olive oil, cereal germ oil, esters of lanolinic acid, esters of oleic acid, esters of lauric acid, esters of stearic acid, fatty esters, higher fatty acids, fatty alcohols, fatty acid modified polysiloxanes, fatty alcohol modified polysiloxanes, polyoxyalkylene modified polysiloxanes, and any combination thereof; Element 30: Element 29 wherein the silicone oil is selected from the group consisting of polydimethylsiloxane, methylphenylpolysiloxane, alkyl modified polydimethylsiloxane, alkyl modified methylphenylpolysiloxane, amino modified polydimethylsiloxane, amino modified methylphenylpolysiloxane, fluorine modified polydimethylsiloxane, fluorine modified methylphenylpolysiloxane, polyether modified polydimethylsiloxane, polyether modified methylphenylpolysiloxane, and any combination thereof; Element 31: The carrier fluid is 0.6 g / cm. 3 ~1.5g / cm 3 and thermoplastic polymers have a density of 0.7 g / cm 3 ~1.7g / cm 3Element 32: the mixing is performed in an extruder; Element 33: the mixing is performed in a stirred reactor; and Element 33: the mixture further comprises a surfactant. Examples of combinations include, but are not limited to, those described with respect to the first non-limiting embodiment, as well as combinations of Element 1 with one or more of Elements 27-33, combinations of Element 3 (and optionally Element 4 and / or Element 5) with one or more of Elements 27-33, combinations of two or more of Elements 27-33, and combinations of one or more of Elements 27-33 with one or more of Elements 1-26.

[0116] section Section 1. A composition comprising a particle comprising a thermoplastic polymer (e.g., a thermoplastic elastomer) and an emulsion stabilizer (e.g., nanoparticles and / or surfactants) associated with an outer surface of the particle.

[0117] Section 2. The composition of section 1, wherein the emulsion stabilizer comprises nanoparticles, at least some of the nanoparticles being embedded in the outer surface of the particle.

[0118] Section 3. The composition of section 1, wherein the thermoplastic polymer is present at 90% to 99.5% by weight of the particles.

[0119] Section 4. The composition of section 1, wherein at least some of the particles have voids that contain an emulsion stabilizer at the void / thermoplastic polymer interface.

[0120] Section 5. The composition of section 4, wherein the emulsion stabilizer comprises nanoparticles, the nanoparticles being embedded at the void / thermoplastic polymer interface.

[0121] Section 6. The composition of section 4, wherein the void contains a dispersion medium having a viscosity of 1,000 cSt to 150,000 cSt at 25°C.

[0122] Section 7. The composition of section 1, wherein the particle further comprises elongated structures on a surface of the particle, the elongated structures comprising a thermoplastic polymer, and an emulsion stabilizer is associated with an outer surface of the elongated structures.

[0123] Section 8. The composition of section 1, wherein the emulsion stabilizer forms a coating that covers less than 5% of the surface of the particles.

[0124] Section 9. The composition of section 1, wherein the emulsion stabilizer forms a coating that covers at least 5% of the surface of the particles.

[0125] Section 10. The composition of section 1, wherein the emulsion stabilizer forms a coating that covers at least 25% of the surface of the particles.

[0126] Section 11. The composition of section 1, wherein the emulsion stabilizer forms a coating that covers at least 50% of the surface of the particles.

[0127] Section 12. The composition of section 1, wherein the particles further comprise a dispersion medium having a viscosity of 1,000 cSt to 150,000 cSt at 25°C.

[0128] Clause 13. The composition of clause 12, wherein the dispersion medium is present at about 5% or less by weight of the particles.

[0129] Section 14. The composition of section 1, wherein the nanoparticles have an average diameter of 1 nm to 500 nm.

[0130] Section 15. Nanoparticles are 10m 2 / g~500m 2 2. The method according to claim 1, having a BET surface area of ​​1. / g.

[0131] Section 16. Thermoplastic polymers include polyamides, polyurethanes, polyethylene, polypropylene, polyacetals, polycarbonates, polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polytrimethylene terephthalate (PTT), polyhexamethylene terephthalate, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyesters (e.g., polylactic acid), polyethers, polyethersulfones, polyetheretherketones, polyacrylates, polymethacrylates, polyimides, acrylonitrile butadiene styrene (ABS), polyphenylene sulfide, vinyl polymers, polyarylene ethers, polyarylene sulfides, polysulfones, polyetherketones, polyamideimides, polyetherimides, polyetheresters, copolymers containing polyether blocks and polyamide blocks (PEBA or polyether block amides), grafted or ungrafted. 2. The composition of claim 1, wherein the polymer is selected from the group consisting of rafted thermoplastic polyolefins, functionalized or non-functionalized ethylene / vinyl monomer polymers, functionalized or non-functionalized ethylene / alkyl (meth)acrylates, functionalized or non-functionalized (meth)acrylic acid polymers, functionalized or non-functionalized ethylene / vinyl monomer / alkyl (meth)acrylate terpolymers, ethylene / vinyl monomer / carbonyl terpolymers, ethylene / alkyl (meth)acrylate / carbonyl terpolymers, methyl methacrylate-butadiene-styrene (MBS) type core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymers, chlorinated or chlorosulfonated polyethylene, polyvinylidene fluoride (PVDF), phenolic resins, poly(ethylene / vinyl acetate), polybutadiene, polyisoprene, styrenic block copolymers, polyacrylonitrile, silicones, and any combination thereof.

[0132] Section 17. The composition according to section 1, wherein the melting point or softening temperature of the thermoplastic polymer is 50°C to 450°C.

[0133] Section 18. The composition according to Section 1, wherein the particles have a D10 of about 0.5 μm to about 125 μm, a D50 of about 1 μm to about 200 μm, and a D90 of about 70 μm to about 300 μm, and D10 < D50 < D90.

[0134] Section 19. The composition according to Section 1, wherein the particles have a diameter span of about 0.2 to about 10.

[0135] Section 20. The composition according to Section 1, wherein the particles have a D10 of about 5 μm to about 30 μm, a D50 of about 30 μm to about 70 μm, and a D90 of about 70 μm to about 120 μm, and D10 < D50 < D90.

[0136] Section 21. The composition according to Section 20, wherein the particles have a diameter span of about 1.0 to about 2.5.

[0137] Section 22. The composition according to Section 1, wherein the particles have a D10 of about 25 μm to about 60 μm, a D50 of about 60 μm to about 110 μm, and a D90 of about 110 μm to about 175 μm, and D10 < D50 < D90.

[0138] Section 23. The composition according to Section 22, wherein the particles have a diameter span of about 0.6 to about 1.5.

[0139] Section 24. The composition according to Section 1, wherein the particles have a D10 of about 75 μm to about 125 μm, a D50 of about 100 μm to about 200 μm, and a D90 of about 125 m to about 300 μm, and D10 < D50 < D90.

[0140] Section 25. The composition according to Section 24, wherein the solidified particles have a diameter span of about 0.2 to about 1.2.

[0141] Section 26. The composition according to Section 1, wherein the particles have a circularity of about 0.90 to about 1.0.

[0142] Section 27. The composition according to Section 1, wherein the particles have a Hausner ratio of about 1.0 to about 1.5.

[0143] Clause 28. The composition of clause 1, wherein the nanoparticles comprise oxide nanoparticles.

[0144] Clause 29. The composition of clause 1, wherein the nanoparticles comprise carbon black.

[0145] Clause 30. The composition of clause 1, wherein the nanoparticles comprise polymeric nanoparticles.

[0146] Clause 31. The composition described in clause 1, wherein the thermoplastic polymer comprises a thermoplastic elastomer.

[0147] Clause 32. The composition described in clause 1, wherein the thermoplastic polymer is a thermoplastic elastomer.

[0148] Section 33. A method comprising: mixing a mixture comprising a thermoplastic polymer (e.g., a thermoplastic elastomer), a dispersion medium immiscible with the thermoplastic polymer, and an emulsion stabilizer at a temperature above the melting point or softening temperature of the thermoplastic polymer and at a shear rate high enough to disperse the thermoplastic polymer in the dispersion medium; cooling the mixture below the melting point or softening temperature of the thermoplastic polymer to form solidified particles comprising the thermoplastic polymer and the emulsion stabilizer associated with an outer surface of the solidified particles; and separating the solidified particles from the dispersion medium.

[0149] Clause 34. The method of clause 33, wherein the emulsion stabilizer comprises nanoparticles, at least a portion of the nanoparticles being embedded in an outer surface of the solidified particle.

[0150] Clause 35. The method of clause 33, wherein at least some of the solidified particles have voids that contain an emulsion stabilizer at the void / thermoplastic polymer interface.

[0151] Clause 36. The method of clause 35, wherein the emulsion stabilizer comprises nanoparticles, the nanoparticles being embedded at the void / thermoplastic polymer interface.

[0152] Clause 37. The method of clause 35, wherein the void contains a dispersion medium.

[0153] Clause 38. The composition of clause 33, wherein the solidified particle further comprises elongated structures on a surface of the solidified particle, the elongated structures comprising a thermoplastic polymer, and the emulsion stabilizer is associated with an outer surface of the elongated structures.

[0154] Clause 39. The composition of clause 33, wherein the emulsion stabilizer forms a coating that covers less than 5% of the surface of the solidified particles.

[0155] Clause 40. The composition of clause 33, wherein the emulsion stabilizer forms a coating that covers at least 5% of the surface of the solidified particles.

[0156] Clause 41. The composition of clause 33, wherein the emulsion stabilizer forms a coating that covers at least 25% of the surface of the solidified particles.

[0157] Clause 42. The composition of clause 33, wherein the emulsion stabilizer forms a coating that covers at least 50% of the surface of the solidified particles.

[0158] Clause 43. The method of clause 33, wherein the thermoplastic polymer is present in the mixture at 5% to 60% by weight of the mixture.

[0159] Clause 44. The method of clause 33, wherein the emulsion stabilizer is present in the mixture at 0.05% to 5% by weight based on the weight of the thermoplastic polymer.

[0160] Clause 45. The method of clause 33, wherein the nanoparticles have an average diameter of 1 nm to 500 nm.

[0161] Section 46. Thermoplastic polymers include polyamides, polyurethanes, polyethylene, polypropylene, polyacetals, polycarbonates, polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polytrimethylene terephthalate (PTT), polyhexamethylene terephthalate, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyesters (e.g., polylactic acid), polyethers, polyethersulfones, polyetheretherketones, polyacrylates, polymethacrylates, polyimides, acrylonitrile butadiene styrene (ABS), polyphenylene sulfide, vinyl polymers, polyarylene ethers, polyarylene sulfides, polysulfones, polyetherketones, polyamideimides, polyetherimides, polyetheresters, copolymers containing polyether blocks and polyamide blocks (PEBA or polyether block amides), grafted or ungrafted. 34. The method of claim 33, wherein the polymer is selected from the group consisting of rafted thermoplastic polyolefins, functionalized or non-functionalized ethylene / vinyl monomer polymers, functionalized or non-functionalized ethylene / alkyl (meth)acrylates, functionalized or non-functionalized (meth)acrylic acid polymers, functionalized or non-functionalized ethylene / vinyl monomer / alkyl (meth)acrylate terpolymers, ethylene / vinyl monomer / carbonyl terpolymers, ethylene / alkyl (meth)acrylate / carbonyl terpolymers, methyl methacrylate-butadiene-styrene (MBS) type core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymers, chlorinated or chlorosulfonated polyethylene, polyvinylidene fluoride (PVDF), phenolic resins, poly(ethylene / vinyl acetate), polybutadiene, polyisoprene, styrenic block copolymers, polyacrylonitrile, silicones, and any combination thereof.

[0162] Clause 47. The method according to clause 33, wherein the melting point or softening temperature of the thermoplastic polymer is between 50°C and 450°C.

[0163] Clause 48. The method of clause 33, wherein the carrier medium is selected from the group consisting of silicone oils, fluorinated silicone oils, perfluorinated silicone oils, polyethylene glycols, alkyl-terminated polyethylene glycols, paraffin, liquid petrolatum, mink oil, turtle oil, soybean oil, perhydrosqualene, sweet almond oil, carophyllum oil, palm oil, pearl oil, grapeseed oil, sesame oil, corn oil, rapeseed oil, sunflower oil, cottonseed oil, apricot oil, castor oil, avocado oil, jojoba oil, olive oil, cereal germ oil, esters of lanolin acid, esters of oleic acid, esters of lauric acid, esters of stearic acid, fatty esters, higher fatty acids, fatty alcohols, fatty acid modified polysiloxanes, fatty alcohol modified polysiloxanes, polyoxyalkylene modified polysiloxanes, and any combination thereof.

[0164] Clause 49. The method of clause 48, wherein the silicone oil is selected from the group consisting of polydimethylsiloxane, methylphenylpolysiloxane, alkyl-modified polydimethylsiloxane, alkyl-modified methylphenylpolysiloxane, amino-modified polydimethylsiloxane, amino-modified methylphenylpolysiloxane, fluorine-modified polydimethylsiloxane, fluorine-modified methylphenylpolysiloxane, polyether-modified polydimethylsiloxane, polyether-modified methylphenylpolysiloxane, and any combination thereof.

[0165] Clause 50. The method of clause 33, wherein the dispersion medium has a viscosity of 1,000 cSt to 150,000 cSt at 25°C.

[0166] Section 51. The dispersion medium is 0.6g / cm 3 ~1.5g / cm 3 and thermoplastic polymers have a density of 0.7 g / cm 3 ~1.7g / cm 3 34. The method of claim 33, wherein the density of the

[0167] Clause 52. The method of clause 33, wherein the mixing is carried out in an extruder.

[0168] Section 53. The method described in Section 33, wherein the mixing is carried out in a stirred reactor.

[0169] Section 54. The method described in Section 33, wherein the mixture further contains a surfactant.

[0170] Section 55. The method described in Section 33, wherein the solidified particles have a D10 of about 0.5 μm to about 125 μm, a D50 of about 1 μm to about 200 μm, and a D90 of about 70 μm to about 300 μm, and D10 < D50 < D90.

[0171] Section 56. The method described in Section 33, wherein the solidified particles have a diameter span of about 0.2 to about 10.

[0172] Section 57. The method described in Section 33, wherein the solidified particles have a D10 of about 5 μm to about 30 μm, a D50 of about 30 μm to about 70 μm, and a D90 of about 70 μm to about 120 μm, and D10 < D50 < D90.

[0173] Section 58. The method described in Section 57, wherein the solidified particles have a diameter span of about 1.0 to about 2.5.

[0174] Section 59. The method described in Section 33, wherein the solidified particles have a D10 of about 25 μm to about 60 μm, a D50 of about 60 μm to about 110 μm, and a D90 of about 110 μm to about 175 μm, and D10 < D50 < D90.

[0175] Section 60. The method described in Section 59, wherein the solidified particles have a diameter span of about 0.6 to about 1.5.

[0176] Section 61. The method described in Section 33, wherein the solidified particles have a D10 of about 75 μm to about 125 μm, a D50 of about 100 μm to about 200 μm, and a D90 of about 125 μm to about 300 μm, and D10 < D50 < D90.

[0177] Section 62. The method described in Section 61, wherein the solidified particles have a diameter span of about 0.2 to about 1.2.

[0178] Clause 63. The method of clause 33, wherein the solidified particles have a circularity of about 0.90 to about 1.0.

[0179] Clause 74. The method of clause 33, wherein the solidified particles have a Hausner ratio of about 1.0 to about 1.5.

[0180] Clause 65. The method of clause 33, wherein the nanoparticles comprise oxide nanoparticles.

[0181] Clause 66. The method of clause 33, wherein the nanoparticles comprise carbon black.

[0182] Clause 67. The method of clause 33, wherein the nanoparticles comprise polymeric nanoparticles.

[0183] Clause 68. The method of clause 33, wherein the thermoplastic polymer comprises a thermoplastic elastomer.

[0184] Clause 69. The method of clause 33, wherein the thermoplastic polymer is a thermoplastic elastomer.

[0185] Unless otherwise indicated, all numbers expressing quantities of ingredients, properties such as molecular weights, process conditions, and the like used in this specification and the related claims should be understood in all instances to be modified by the term "about." Accordingly, unless indicated to the contrary, the numerical parameters set forth in the following specification and appended claims are approximations that may vary depending on the desired properties sought to be obtained by embodiments of the present invention. At the very least, and without attempting to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should be construed in light of the number of reported significant digits and by applying ordinary rounding techniques.

[0186] One or more exemplary embodiments incorporating embodiments of the invention disclosed herein are presented herein. For clarity, not all features of a physical implementation are described or shown in this application. It is understood that in developing a physical embodiment incorporating an embodiment of the invention, numerous implementation-specific decisions must be made to achieve the developer's goals, such as compliance with system-related, business-related, government-related, and other constraints, which vary from implementation to implementation and from time to time. Although the developer's efforts may be time-consuming, such efforts would nevertheless be routine for one of ordinary skill in the art having the benefit of this disclosure.

[0187] Although the compositions and methods are described herein in terms of "comprising" various components or steps, the compositions and methods may also "consist essentially of" or "consist of" the various components and steps.

[0188] To facilitate a better understanding of the embodiments of the present invention, the following examples of preferred or representative embodiments are given. The following examples should not be read to limit or define the scope of the present invention. EXAMPLES

[0189] Example 1. Polyamide 6 microparticles were produced in a Haake small-scale twin-screw extruder with a high shear rotor. The dispersion medium was PDMS oil with a viscosity of either 30,000 cSt or 60,000 cSt at room temperature. The concentrations of the components in the final mixture in the extruder are shown in Table 1. The order of addition of the components to the extruder was either (a) the dispersion medium was added to the extruder, brought to temperature, and then polymer pellets at room temperature were added to the heated dispersion medium in the extruder, or (b) the polymer pellets were added to the extruder, brought to temperature, and then dispersion medium at room temperature was added to the molten polymer in the extruder. At temperature (see Table 1), the extruder was operated at 200 rpm for 30 minutes. The mixture was then discharged from the extruder onto a cold surface to effect rapid cooling. The torque of the extruder system was measured during heating, at temperature, and cooling, but no significant torque was detected.

[0190] [Table 1]

[0191] The resulting mixture was then filtered through a 90 mm WHATMAN® #1 paper filter (available from SigmaAldrich) to separate the polyamide 6 particles from the dispersion medium. The particles were washed three times with 300 mL of ethyl acetate. The particles were then air-dried overnight in an aluminum pan in a fume hood.

[0192] The polyamide 6 particles were then characterized for size with a Malvern MASTERSIZER™ 3000 and for morphology with SEM micrographs.

[0193] [Table 2]

[0194] The examples showed the general trends that (a) increasing oil viscosity decreases particle size and diameter span (e.g., compare 1-1 with 1-3 and 1-6 with 1-5), (b) increasing polymer loading increases particle size and decreases diameter span (e.g., compare 1-4 with 1-5 and 1-1 with 1-7), and (c) increasing processing temperature decreases particle size and diameter span (e.g., compare 1-8 with 1-5 and 1-1 with 1-2).

[0195] Additionally, inductively coupled plasma was performed on particles digested in HNO3 / HF / H2O2 mixtures using a closed vessel microwave or oven for digestion to determine the silica content associated with the residual PDMS. The amount of silica found in the nine samples ranged from about 234 ppm to about 374 ppm. For the sample with about 234 ppm silica, it is estimated that there is only about 0.62 g of PDMS per 1000 g of particles. Without wishing to be bound by theory, it is believed that the PDMS is primarily present on the surface of the particles.

[0196] Example 2. Polyamide 12 microparticles were produced in a 25 mm twin screw extruder (Werner & Pfleiderer ZSK-25). The carrier fluid was PDMS oil with a viscosity of 10,000 cSt at room temperature. The concentrations of the components in the final mixture in the extruder are shown in Table 3. Polymer pellets were added to the extruder, brought to temperature, and then preheated carrier liquid with AEROSIL® R812S silica nanoparticles dispersed therein was added to the molten polymer in the extruder. Other operating parameters are shown in Table 3. The mixture was then discharged into a container and allowed to cool to room temperature over several hours. Light scattering particle size data is also shown in Table 3.

[0197] [Table 3]

[0198] Example 3. ELASTOLLAN® 1190A10 thermoplastic polyurethane (TPU) was added to a 25 mm twin screw extruder (Werner & Pfleiderer ZSK-25), brought to temperature, and then preheated 10,000 cSt PDSM oil having AEROSIL® RX50 silica nanoparticles dispersed therein was added to the molten polymer in the extruder. The extruder conditions and results are shown in Table 4.

[0199] [Table 4]

[0200] Example 4. Polyamide 6 particles were prepared by melt emulsification using a 1 L stirred reactor manufactured by Parr Instruments. The reactor was charged with 20 wt% polyamide 6 and 80 wt% 10,000 cSt PDMS oil. The mixture was then heated to 225°C while stirring at 1000 rpm using two 4-blade propellers. After about 60 minutes, the mixture was discharged from the reactor onto dry ice to quench the mixture. The mixture was then filtered and washed to recover the polymer particles. The resulting polymer particles were passed through a 150 μm sieve. About 40 wt% of the polyamide 6 charged to the reactor was passed through a 150 μm sieve. Figure 11 is an SEM micrograph of the particles after sieving, showing the large range of particle sizes.

[0201] Example 5. Polyamide 12 particles were prepared by melt emulsification using a 2 L glass reactor manufactured by Buchi AG. The reactor was loaded with 1 wt% AEROSIL® R812S silica nanoparticles (relative to the weight of polyamide 12 in the final mixture) in 10,000 cSt PDMS oil. The mixture was heated to 200°C, after which 23 wt% polyamide 12 pellets were added relative to the combined weight of PDMS oil and polyamide 12. The reactor was mixed at 500 rpm for 30 minutes. The resulting mixture was discharged and cooled to ambient temperature at a rate of about 1°C to about 3°C ​​per minute. The mixture was then washed with heptane and filtered through a 90 mm WHATMAN® #1 paper filter to recover the polymer particles. The resulting polymer particles were air-dried overnight in a fume hood. The dried particles have a D50 of about 227 μm, and the dried particles that passed through a 150 μm sieve have a D50 of about 124 μm.

[0202] Example 6. Polyamide 12 particles (Examples 6-1 to 6-44) were prepared by melt emulsification in a 1 L glass kettle reactor. 10,000 cSt PDMS oil, 23% polyamide 12 (RTP, EMX-Grivory, or Arkema) based on the combined weight of PDMS oil and polyamide 12, and the desired amount of silica nanoparticles (AEROSIL® R812S or AEROSIL® RX50) based on the weight of polyamide 12 were added to a glass kettle. The order of addition was either (c) PDMS oil and silica nanoparticles were mixed to a good dispersion and then polyamide was added, or (d) PDMS oil, polyamide, and silica nanoparticles were added before mixing. The nitrogen headspace purge was then turned on and the mixture was heated to the desired temperature (e.g., 200°C, 210°C, or 220°C) at 260 rpm for 90 minutes. Once at temperature, the rotor speed was increased to the desired RPM. Samples were taken at various times. Upon completion, the heating and stirring were stopped and the reactor was allowed to cool to room temperature before discharging the mixture. The resulting mixture was filtered and washed with heptane. The resulting particles were allowed to air dry overnight in a fume hood. Optionally, the dried particles were scr'd through a 150 μm sieve. Table 5 lists the experimental details and the resulting particle properties.

[0203] For samples 6-45 to 6-47, polyamide 12 particles were prepared by melt emulsification using a 2 L stainless steel reactor from Buchi AG. The reactor was filled with 0.67 wt% Aerosil® R812S silica nanoparticles (relative to the weight of polyamide 12 in the final mixture) in 60,000 cSt PDMS oil and sealed without N2 purging. The mixture was heated to 250°C at a ramp rate of 3.68°C / min, after which 30 wt% polyamide 12 pellets were added relative to the combined weight of PDMS oil and polyamide 12. When the reactor temperature reached 245°C, the vent valve was slowly opened and the reactor was purged with N2 at a flow rate of 2-3 scfh. The reactor was mixed at 650 rpm for 60 minutes. The resulting mixture was cooled to below 60°C with gentle stirring at 50 rpm and discharged. Process samples taken at 40 minutes, 60 minutes, and final room temperature were then washed with heptane and filtered through a 90 mm WHATMAN® #1 paper filter to recover the polymer particles. The resulting polymer particles were air-dried overnight in a fume hood. The dried particles had a D50 of about 21.3 μm, and the final dried particles passed through a 150 μm sieve had a D50 of about 21.5 μm.

[0204] For samples 6-48 to 6-50, polyamide 12 particles were prepared by melt emulsification using a 2 L stainless steel reactor from Buchi AG. The reactor was loaded with 0.67 wt% AEROSIL® R812S silica nanoparticles (relative to the weight of polyamide 12 in the final mixture) in 60,000 cSt PDMS oil and purged with N2 at a flow rate of 2-3 scfh. The mixture was heated to 250°C at a ramp rate of 3.68°C / min, followed by the addition of 30 wt% polyamide 12 pellets relative to the combined weight of PDMS oil and polyamide 12. The reactor was mixed at 650 rpm for 60 minutes. The resulting mixture was cooled to below 60°C with gentle stirring at 50 rpm and discharged. Process samples taken at 50 min, 60 min, and room temperature were then washed with heptane and filtered through a 90 mm WHATMAN® #1 paper filter to recover the polymer particles. The final room temperature sample was agglomerated and the particle size was not measured. The resulting polymer particles taken at 60 minutes were air dried overnight in a fume hood. The dried particles have a D50 of about 25.8 μm and the dried particles passed through a 150 μm sieve have a D50 of about 26.4 μm.

[0205] For samples 6-51 to 6-53, polyamide 12 particles were prepared by melt emulsification using a 2 L stainless steel reactor from Buchi AG. The reactor was loaded with 0.67 wt% AEROSIL® R812S silica nanoparticles (relative to the weight of polyamide 12 in the final mixture) in 60,000 cSt PDMS oil and purged with N2 at a flow rate of 2-3 scfh. The mixture was heated to 250°C at a ramp rate of 5.68°C / min, followed by the addition of 30 wt% polyamide 12 pellets relative to the combined weight of PDMS oil and polyamide 12. The reactor was mixed at 650 rpm for 60 minutes. The resulting mixture was cooled to below 60°C with gentle stirring at 50 rpm and discharged. Process samples taken at the 60 minute time point and at room temperature were then washed with heptane and filtered through a 90 mm WHATMAN® #1 paper filter to recover the polymer particles. The final room temperature sample was agglomerated and the particle size was not measured. The resulting polymer particles taken at 60 minutes were air dried overnight in a fume hood. The dried particles have a D50 of about 33.8 μm and the dried particles passed through a 150 μm sieve have a D50 of about 34.9 μm.

[0206] [Table 5-1]

[0207] [Table 5-2]

[0208] [Table 5-3]

[0209] Figure 12 shows an SEM micrograph of sample 6-4. Figure 13 shows an SEM micrograph of sample 6-10. Figure 14 shows an SEM micrograph of sample 6-15. Figure 15 shows an SEM micrograph of sample 6-26. Figure 16 shows an SEM micrograph of sample 6-30. Figures 17-20 show SEM micrographs of samples 6-31, 6-32, 6-33, and 6-34.

[0210] This example shows that decreasing the concentration of silica nanoparticles in the mixture increases the particle size but decreases the diameter span (e.g., compare 6-17 to 6-18 with 6-28 to 6-29). Furthermore, increasing the temperature decreases the particle size but increases the diameter span (e.g., compare 6-17 to 6-18, 6-20 to 6-21, and 6-24 to 6-25). It is also clear that mixing times greater than about 10 minutes have minimal effect on particle size and diameter span.

[0211] Example 7. SEM micrographs were taken of commercially available polyamide particulate material used for 3D printing. See Table 6.

[0212] [Table 6]

[0213] Comparing the SEM micrographs of the commercial samples with those of Samples 6-4, 6-10, 6-15, 6-26, 6-30, 6-31, 6-32, 6-33, and 6-34 of Example 4, the particles produced by the methods described herein have greater circularity and higher silica nanoparticle coverage on the surface of the polyamide particles.

[0214] Example 8. Three sets of samples were prepared using polyamide 12 from RTP. 10,000 cSt PDMS, 23 wt% polyamide 12 based on the combined weight of PDMS and polyamide, 1 wt% Aerosil® R812S silica nanoparticles based on the weight of polyamide, and optionally surfactant (wt% based on the weight of polyamide) were placed in a glass kettle reactor. The headspace was purged with argon and the reactor was maintained under positive argon pressure. The components were heated to above 220° C. for approximately 60 minutes with stirring at 300 rpm. At temperature, the rpm was increased to 1250 rpm. The process was stopped after 90 minutes and allowed to cool to room temperature with stirring. The resulting mixture was filtered and washed with heptane. A portion of the resulting particles was screened (scr) through a 150 μm sieve. Table 7 includes additional components of the mixture and properties of the resulting particles.

[0215] [Table 7]

[0216] 25 and 26 are the volume density particle size distributions of screened and unscreened particles, respectively.

[0217] Example 9. This example shows that surfactant inclusion and composition can be another tool used to tailor particle characteristics.

[0218] In this example, the powder flow of polyurethane microparticles was characterized through sieving and angle of repose measurement. The sieving yield of polyurethane microparticles was determined by passing a certain amount of polyurethane microparticles through a 150 μm American standard sieve (ASTM E11) and determining the mass fraction of the microparticles that passed through the sieve relative to the total amount of polyurethane microparticles. The sieve was used manually without any specific condition of the duration of force. The angle of repose measurement was performed using a Hosokawa Micron Powder Characteristics Tester PT-R using ASTM D6393-14 "Standard Test Method for Bulk Solids Characterized by Carr Indices".

[0219] In this example, the average particle size measurements and particle size distributions were measured by optical digital microscopy. Optical images were obtained using a Keyence VHX-2000 digital microscope using version 2.3.5.1 software for particle size analysis (system version 1.93). In some cases, D 10 , D 50 , and D 90 Measurements were performed using a Malvern MASTERSIZER™ 3000 Aero S particle size analyzer which uses a light scattering technique for particle size measurement.

[0220] For light scattering techniques, glass bead control samples with diameters in the range of 15 μm to 150 μm under the trade name Quality Audit Standards QAS4002™ obtained from Malvern Analytical Ltd. can be used. Samples can be analyzed as dry powders dispersed in air using the dry powder dispersion module of a MASTERSIZER™ 3000 Aero S. Particle size can be derived using the instrument software from a plot of volume density as a function of size.

[0221] Comparative Example 9-1. To a 500 mL glass reactor, 160 g of polydimethylsiloxane (PSF-30000, Clearco) was added. The reactor was set at an agitation speed of 200 rpm and the temperature was increased to 190° C. under a nitrogen gas atmosphere. Further heating was performed to 200° C. at which point 40 g of thermoplastic polyurethane pellets were added to the stirred polydimethylsiloxane. The thermoplastic polyurethane was poly[4,4′-methylenebis(phenylisocyanate)-alt-1,4-butanediol / di(propylene glycol) / polycaprolactone] having a hardness of Shore A 84 (Sigma-Aldrich). After the thermoplastic polyurethane pellets were thoroughly combined with the polydimethylsiloxane, the agitation speed was increased to 500 rpm and the temperature was maintained at 200° C. for 60 minutes. Agitation was then discontinued and the resulting slurry was allowed to cool to room temperature. The slurry was washed twice with hexane and the thermoplastic polyurethane microparticles were obtained after vacuum filtration.

[0222] Then, the thermoplastic polyurethane microparticles are passed through a 150 μm sieve, and the microparticles that pass through the sieve are characterized by optical imaging. Figure 27 shows an exemplary optical microscope image of the thermoplastic polyurethane microparticles obtained in Comparative Example 9-1 at 150X magnification. The average particle size is about 100 μm, and a wide particle size distribution is obtained.

[0223] Comparative Example 9-2. The thermoplastic polyurethane microparticles of Comparative Example 9-1 were collected after filtration and before sieving, and combined with 0.25 wt% fumed silica microparticles functionalized with hexamethyldisilazane (AEROSIL® RX50). The thermoplastic polyurethane microparticles were then dry blended with the fumed silica microparticles using an SKM Mill at a blending speed of 170 rpm for 30 seconds.

[0224] The dry blended microparticles were then passed through a 150 μm sieve and characterized by optical imaging and SEM. Figure 28 shows exemplary optical microscope images of the thermoplastic polyurethane microparticles obtained in Comparative Example 9-2. Figures 29A and 29B show exemplary SEM images of the thermoplastic polyurethane microparticles obtained in Comparative Example 9-2 at various magnifications. As in Comparative Example 9-1, the average particle size was about 100 μm, and a wide distribution of particle sizes was obtained. There was no evidence of silica particles embedded on the surface of the thermoplastic polyurethane microparticles. Furthermore, there was no obvious formation of a uniform silica coating on the polyurethane microparticles.

[0225] Example 9-1. Comparative Example 9-1 was repeated, except that 0.25 wt. % fumed silica microparticles functionalized with hexamethyldisilazane (AEROSIL® R812S) were combined with the polydimethylsiloxane before the reactor was heated to temperature and the thermoplastic polyurethane microparticles were added.

[0226] Then, the thermoplastic polyurethane microparticles are passed through a 150 μm sieve, and the microparticles that pass through the sieve are characterized by optical imaging. Figure 30 shows an exemplary optical microscope image of the thermoplastic polyurethane microparticles obtained in Example 9-1. The average particle size is about 12±16 μm. Figure 31 shows an exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 9-1.

[0227] Example 9-2. Example 9-1 was repeated, except that 1.00 wt% of the same fused silica particulate was used. In addition, the slurry was washed with hexane three times instead of two times.

[0228] Then, the thermoplastic polyurethane microparticles are passed through a 150 μm sieve, and the microparticles that pass through the sieve are characterized by optical imaging. Figure 32 shows an exemplary optical microscope image of the thermoplastic polyurethane microparticles obtained in Example 9-2. The average particle size is about 34±19 μm. Figure 33 shows an exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 9-2.

[0229] Example 9-3. Example 9-1 was repeated, except that the type of fumed silica particulate was changed to AEROSIL® RX 50. In addition, the slurry was washed four times with heptane instead of twice with hexane.

[0230] The thermoplastic polyurethane microparticles were then passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging and SEM. Figure 34 shows an exemplary optical microscope image of the thermoplastic polyurethane microparticles obtained in Example 9-3. Figures 35A and 35B show exemplary SEM images of the thermoplastic polyurethane microparticles obtained in Comparative Example 9-3 at various magnifications. The average particle size by optical imaging was about 48±20 μm, and the angle of repose was 32.0°. Figure 36 shows an exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 9-3.

[0231] The particle size distributions measured by a Malvern Mastersizer particle size analyzer were D of 40.7 μm, 68.2 μm and 109 μm, respectively. 10 Value, D 50 value, and D 90 values ​​were provided, thereby resulting in a span of 1.001.

[0232] Example 9-4. Example 9-1 was repeated, except that the type of thermoplastic polyurethane pellets was changed to ELASTOLLAN® 1190A obtained from BASF. ELASTOLLAN® 1190A is a polyether polyurethane elastomer having a hardness of 90 Shore A.

[0233] The thermoplastic polyurethane microparticles were then passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging and SEM. Figure 37 shows exemplary optical microscope images of the thermoplastic polyurethane microparticles obtained in Example 9-4. Figures 38A-38D show exemplary SEM images of the thermoplastic polyurethane microparticles obtained in Example 9-4 at various magnifications. The average particle size by optical imaging was about 68±29 μm, and the angle of repose was 29.9°. Figure 39 shows an exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 9-4.

[0234] The particle size distributions measured by a Malvern Mastersizer particle size analyzer were D of 61.0 μm, 95.6 μm, and 146 μm, respectively. 10 , D 50 , and D 90 This provided a value of 0.889, thereby resulting in a span of 0.889.

[0235] Example 9-5. Example 9-4 was repeated except that the process was carried out at half the scale of Example 9-4.

[0236] The thermoplastic polyurethane microparticles were then passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging and SEM. Figure 40 shows exemplary optical microscope images of the thermoplastic polyurethane microparticles obtained in Example 9-5. Figures 41A-41C show exemplary SEM images of the thermoplastic polyurethane microparticles obtained in Example 9-5 at various magnifications. The average particle size by optical imaging was about 61±17 μm. Figure 42 shows an exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 9-5.

[0237] The particle size distributions measured by a Malvern MASTERSIZER™ particle size analyzer were D of 52.6 μm, 71.7 μm, and 97.2 μm, respectively. 10 , D 50 , and D 90 This provided a value of 0.622, thereby resulting in a span of 0.622.

[0238] Comparison of Results. Tables 8A and 8B below summarize the forming conditions used for Comparative Examples 9-1 and 9-2 and Examples 9-1 to 9-5, and the properties of the thermoplastic polyurethane microparticles obtained in each case. The mass of the thermoplastic polyurethane was calculated by dividing the combined mass of the thermoplastic polyurethane and polydimethylsiloxane.

[0239] [Table 8A]

[0240] [Table 8B]

[0241] As shown in Tables 8A and 8B and the attached figures, in the absence of fused silica emulsion stabilizer, there was a broad particle size distribution and some particle coalescence (Comparative Examples 9-1 and 9-2). Different loadings and sizes of fused silica particles resulted in narrower particle size distributions and variation in average particle size (Examples 9-1 to 9-3). Different thermoplastic polyurethanes also resulted in variation in the resulting average particle size (Examples 9-3 and 9-4). Processing scale also affected the particle size distribution (Examples 9-4 and 9-5).

[0242] Comparing the SEM images, there was a very uniform coverage of silica nanoparticles on the surface of the thermoplastic polyurethane microparticles obtained by melt emulsification (Examples 9-3 to 9-5, Figures 35A / 10B, 38A to 13D, and 41A to 41C). The thermoplastic polyurethane microparticles obtained in Example 9-5, which have a narrower particle size distribution, had a more uniform coverage / distribution of silica nanoparticles compared to the comparative thermoplastic polyurethane microparticles prepared in Example 9-4, which have a wider particle size distribution.

[0243] In contrast to thermoplastic polyurethane microparticles produced by melt emulsification with silica nanoparticles, dry blending of thermoplastic polyurethane microparticles with silica nanoparticles resulted in little, if any, coverage of silica nanoparticles on the thermoplastic polyurethane microparticles (Comparative Example 9-2, Figures 29A / 29B).

[0244] Another comparative example of thermoplastic polyurethane microparticles is ADSINT TPU 90A NAT from ADVANC3D, a 3D printing composition. ADSINT TPU 90A NAT thermoplastic polyurethane microparticles have irregular particle shapes, as shown in the SEM images of Figures 43A-43E. Based on the SEM images of Figures 43B and 43C, there is a non-uniform distribution of emulsion stabilizer on the surface of the ADSINT TPU 90A microparticles. Microparticles that are irregular in shape and have rough surfaces tend to have a non-uniform distribution of emulsion stabilizer on the surface, as shown in the SEM images of Figures 43C and 43D, and agglomerations may occur in the rough areas and crevices. The cross-sectional SEM image of Figure 43E shows the presence of emulsion stabilizer in confined areas with a non-uniform distribution around the particle.

[0245] As produced in Examples 9-1 to 9-5, the substantially spherical microparticles with smooth surfaces can provide homogeneous incorporation of emulsion stabilizer around the outer surface of each microparticle.The substantially homogeneous incorporation of emulsion stabilizer on the microparticles can help achieve uniform properties and consistent performance of the corresponding bulk material, such as powder flow properties and processing properties.

[0246] Example 10. Selective laser sintering (SLS) was carried out using Snow White SLS printer system (Sharebot). The thermoplastic polyurethane particulates of Example 9-3 were deposited in a 30mm x 30mm square using SLS printer system, and then sintered under various laser output conditions as shown in Table 9 below. The porosity after sintering was calculated using digital microscope software.

[0247] [Table 9]

[0248] As shown, effective sintering was achieved with laser powers above 20%, up to 40% power (highest value tested), resulting in low-porosity materials with less than 1% porosity, often less than 0.1% porosity. The observed powder formation is believed to artificially lower the amount of porosity measured. In either case, low porosity is a characteristic that effectively fuses thermoplastic polyurethane particulates together. As a representative example, FIG. 44 shows an optical image of a print obtained from entry 5 of Example 10.

[0249] Example 11. In this example, the powder flow of polyurethane microparticles was characterized through sieving and angle of repose measurement. The sieving yield of polyurethane microparticles was determined by passing a certain amount of polyurethane microparticles through a 150 μm US standard sieve and determining the mass fraction of the microparticles that passed through the sieve relative to the total amount of polyurethane microparticles. The sieve was used manually without any specific condition of the duration of force. The angle of repose measurement was performed using a Hosokawa Micron Powder Characteristics Tester PT-R using ASTM D6393-14 "Standard Test Method for Bulk Solids Characterized by Carr Indices".

[0250] In this example, the average particle size (D 50 ), D 10 and D. 90 Measurements were made using a Malvern MASTERSIZER™ 3000 Aero S particle size analyzer. Optical images were obtained using a Keyence VHX-2000 digital microscope using version 2.3.5.1 software for particle size analysis (system version 1.93). The optical images were also processed to obtain the average particle size.

[0251] Comparative Example 11-1. To a 500 mL glass reactor, 160 g of polydimethylsiloxane (PSF-30000, Clearco) was added. The reactor was set at an agitation speed of 350 rpm using an overhead stirrer and the temperature was increased to 190° C. It was further heated to 200° C. at which point 40 g of thermoplastic polyurethane pellets were added to the stirred polydimethylsiloxane. The thermoplastic polyurethane was poly[4,4'-methylenebis(phenylisocyanate)-alt-1,4-butanediol / di(propylene glycol) / polycaprolactone] (Sigma-Aldrich). After the thermoplastic polyurethane pellets were completely combined with the polydimethylsiloxane, the agitation speed was increased to 500 rpm and the temperature was maintained at 200° C. for 60 minutes. The agitation was then discontinued and the resulting slurry was allowed to cool to room temperature. The slurry was washed four times with heptane to obtain thermoplastic polyurethane microparticles after vacuum filtration.

[0252] The thermoplastic polyurethane microparticles were then passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Figure 45 shows an exemplary optical microscope image of the thermoplastic polyurethane microparticles obtained in Comparative Example 11-1 at 150X magnification. The average particle size was 97.1 μm, and a wide distribution of particle sizes was obtained (span=1.239). Figure 46 shows an exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Comparative Example 11-1.

[0253] Comparative Example 11-2. In a 500 mL glass reactor, 320 g of polydimethylsiloxane (PSF-30000, Clearco) was added to 0.25 wt. % fumed silica fine particles functionalized with hexamethyldisilazane (AEROSIL® RX50, 35±10 m 2The reactor was set to an agitation speed of 200 rpm using an overhead stirrer and the temperature was increased to 190° C. Heating was continued to 200° C. at which point 80 g of thermoplastic polyurethane pellets were added to the stirred polydimethylsiloxane. The thermoplastic polyurethane in this case was ELASTOLLAN® 1190A, a polyether polyurethane elastomer obtained from BASF. After the thermoplastic polyurethane pellets were fully combined with the polydimethylsiloxane, the agitation speed was increased to 500 rpm and the temperature was maintained at 200° C. for 60 minutes. Agitation was then discontinued and the resulting slurry was allowed to cool to room temperature. The slurry was washed four times with hexane to obtain thermoplastic polyurethane microparticles after vacuum filtration.

[0254] The thermoplastic polyurethane microparticles were then passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Figure 47 shows an exemplary optical microscope image of the thermoplastic polyurethane microparticles obtained in Comparative Example 11-2 at 150X magnification. The average particle size was 95.6 μm, and a wide distribution of particle sizes was obtained (span=0.892). The angle of repose was 29.9°. Figures 48A and 48B show exemplary SEM images of the thermoplastic polyurethane microparticles obtained in Comparative Example 11-2 at various magnifications. Figure 49 shows an exemplary histogram of particle size of the thermoplastic polyurethane microparticles obtained in Comparative Example 11-2.

[0255] Comparative Example 11-3. Comparative Example 11-1 was repeated, except that 1.0 wt. % poly[dimethylsiloxane-co-[3-(2-(2-hydroxyethoxy)ethoxy)propylmethylsiloxane] surfactant was mixed with the PDMS prior to heating to the processing temperature. FIG. 50 shows an exemplary optical microscope image at 100X magnification of the thermoplastic polyurethane microparticles obtained in Comparative Example 11-3. The average particle size was 123 μm, and a broad distribution of particle sizes was obtained (span=0.977). FIG. 51 shows an exemplary histogram of particle sizes of the thermoplastic polyurethane microparticles obtained in Comparative Example 11-3.

[0256] Comparative Example 11-4. Comparative Example 11-1 was repeated, except that 2.5 wt. % SPAN® 80 (sorbitan maleate nonionic surfactant) was mixed with the PDMS before heating to the processing temperature. Figure 52 shows an exemplary optical microscope image at 100X magnification of the thermoplastic polyurethane microparticles obtained in Comparative Example 11-4. The average particle size was 139 μm, and a wide distribution of particle sizes was obtained (Span=0.811). Figure 53 shows an exemplary histogram of particle sizes of the thermoplastic polyurethane microparticles obtained in Comparative Example 11-4.

[0257] Example 11-1. Comparative Example 11-1 was repeated, except that 0.25 wt. % fumed silica microparticles functionalized with hexamethyldisilazane (AEROSIL® RX50) and 1.0 wt. % sodium dodecyl sulfate (SDS) were mixed with the PDMS before heating to the processing temperature. Figure 54 shows an exemplary optical microscope image at 300X magnification of the thermoplastic polyurethane microparticles obtained in Example 11-1. The average particle size was 26.8 μm, and a wide distribution of particle sizes was obtained (span=1.251). Figure 55 shows an exemplary histogram of particle sizes of the thermoplastic polyurethane microparticles obtained in Example 11-1.

[0258] Example 11-2. Comparative Example 11-1 was repeated, except that 0.25 wt. % fumed silica particulate functionalized with hexamethyldisilazane (AEROSIL® RX50) and 2.5 wt. % docusate sodium (sodium 1,4-bis(2-ethylhexoxy)-1,4-dioxobutane-2-sulfonate, also known as dioctyl sodium sulfosuccinate) were combined with the polydimethylsiloxane before the reactor was heated to temperature and the thermoplastic polyurethane polymer was added.

[0259] After isolation, the thermoplastic polyurethane microparticles were passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Figure 56 shows an exemplary optical microscope image of the thermoplastic polyurethane microparticles obtained in Example 11-2 at 150X magnification. The average particle size was 31.5 μm, and a relatively narrow distribution of particle sizes was obtained (span=0.859). The angle of repose was 38.2°. Figure 57 shows an exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 11-2.

[0260] Example 11-3. Comparative Example 11-1 was repeated, except that 1.0 wt. % fumed silica particulate functionalized with hexamethyldisilazane (AEROSIL® RX50) and 1.0 wt. % docusate sodium were combined with the polydimethylsiloxane before the reactor was heated to temperature and the thermoplastic polyurethane polymer was added.

[0261] After isolation, the thermoplastic polyurethane microparticles were passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Figure 58 shows an exemplary optical microscope image of the thermoplastic polyurethane microparticles obtained in Example 11-3 at 150X magnification. The average particle size was 51.2 μm, and a relatively narrow distribution of particle sizes was obtained (span=0.777). The angle of repose was 32.6°. Figure 59 shows an exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 11-3.

[0262] Example 11-4. Comparative Example 11-1 was repeated, except that 0.25 wt. % fumed silica particulate (AEROSIL® RX50) functionalized with hexamethyldisilazane and 5 wt. % CALFAX® DB-45 were combined with the polydimethylsiloxane before the reactor was heated to temperature and the thermoplastic polyurethane polymer was added.

[0263] After isolation, the thermoplastic polyurethane microparticles were passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Figure 60 shows an exemplary optical microscope image of the thermoplastic polyurethane microparticles obtained in Example 11-4 at 150X magnification. The average particle size was 121 μm, and a relatively narrow distribution of particle sizes was obtained (span=0.435). Figures 61A and 61B show exemplary SEM images of the thermoplastic polyurethane microparticles obtained in Comparative Example 11-4 at various magnifications. Figure 62 shows an exemplary histogram of particle sizes of the thermoplastic polyurethane microparticles obtained in Example 11-4.

[0264] Example 11-5. Comparative Example 11-1 was repeated, except that 1.0 wt. % fumed silica particulate (AEROSIL® RX50) functionalized with hexamethyldisilazane and 2.5 wt. % CALFAX® DB-45 were combined with the polydimethylsiloxane before the reactor was heated to temperature and the thermoplastic polyurethane polymer was added.

[0265] After isolation, the thermoplastic polyurethane microparticles were passed through a 150 μm sieve, and the microparticles that passed through the sieve were characterized by optical imaging. Figure 63 shows an exemplary optical microscope image of the thermoplastic polyurethane microparticles obtained in Example 11-5 at 150X magnification. The average particle size was 62.9 μm, and a relatively narrow distribution of particle sizes was obtained (span=0.619). The angle of repose was 31.3°. Figure 64 shows an exemplary histogram of the particle size of the thermoplastic polyurethane microparticles obtained in Example 11-5.

[0266] Comparison of Results. Table 10 summarizes the forming conditions used for Comparative Examples 11-1 to 11-4, and the properties of the thermoplastic polyurethane microparticles obtained in each case. Table 11 summarizes the forming conditions used for Examples 11-1 to 11-5, and the properties of the thermoplastic polyurethane microparticles obtained in each case.

[0267] [Table 10]

[0268] [Table 11]

[0269] The combination of silica nanoparticles and sulfonate surfactant was effective in forming elastomeric microparticles with narrow size distribution (span <0.9), with yields after sieving of the original unsieved product of greater than 90% (Examples 11-2 to 11-5). The sulfate surfactant (Example 11-1), in contrast, produced a much broader particle size distribution, albeit with similar particle sizes to those produced with the sulfonate surfactant. The elastomeric microparticles formed in the absence of silica nanoparticles were significantly larger in size and had lower yields after sieving (Comparative Examples 11-1, 11-3, and 11-4).

[0270] Figure 65 shows exemplary particle size distribution plots for Comparative Examples 11-1 and 11-4 and Example 11-3. As shown, the use of silica particles and a sulfonate surfactant (Examples 11-3) resulted in a much narrower particle size distribution.

[0271] Example 12. Selective laser sintering (SLS) was carried out using a Snow White SLS printer system (Sharebot). The thermoplastic polyurethane particulates of Example 11-3 were deposited in a 30 mm x 30 mm square using an SLS printer system, and then sintered under various laser power conditions as shown in Table 12 below. The porosity after sintering was calculated using digital microscope software. Little or no caking was observed after sintering. This may indicate good single layer sintering performance.

[0272] [Table 12]

[0273] As shown, effective sintering was achieved at laser powers above 20%, up to 45% power (highest value tested), resulting in low porosity material with small amounts of voids, and less than 1.5% voids at laser powers above 30%. Low porosity is a characteristic that allows thermoplastic polyurethane particulates to be effectively fused together. It is believed that the powder formation of entry 6 artificially reduces the amount of voids measured.

[0274] Table 13 compares the laser sintering performance of the thermoplastic polyurethane particulate of Example 11-3 with that of Comparative Example 11-2 and the commercially available ADSINT polyurethane particulate.

[0275] [Table 13]

[0276] As shown, when using the thermoplastic polyurethane microparticles of Example 11-3, effective sintering was achieved at laser powers above 20%, up to 45% power (the highest value tested), resulting in low porosity materials. The laser sintering performance of the thermoplastic polyurethane microparticles of Example 11-3, as assessed by the resulting porosity, was significantly better than that of the commercially available ADSINT thermoplastic polyurethane microparticles. The laser sintering performance of the thermoplastic polyurethane microparticles of Example 11-3 was also superior to Comparative Example 11-2 in terms of being sinterable at lower laser powers, resulting in lower porosity values ​​in most cases. As a representative example, FIG. 66 shows an optical image of the print obtained from entry 5 of Table 12 (40% laser power).

[0277] Example 13. To a 500 mL glass kettle reactor equipped with a heating mantle, 140 g of PDMS (PSF-10000), 0.6 g (1.0 wt%) of AEROSIL RX50 silica nanoparticles, and 60 g of HYTREL® HTR 6108 pellets (glycol modified polyethylene terephthalate, available from DuPont) were added. The reactor was set to an agitation speed of 200 RPM and the temperature was increased to 200° C. over 30 minutes with an argon purge. Once the temperature reached 200° C., the agitation speed was increased to 1000 RPM. After 60 minutes, the heating and agitation were discontinued and the slurry was allowed to cool to room temperature. The slurry was then washed three times with heptane and the microparticles were isolated by vacuum filtration. After drying overnight under vacuum, the microparticles were then sieved through a 150 μm filter. For the microparticles produced, the average particle size (measured by optical microscopy) was 57 μm, the span was 0.87, and the angle of repose was 29.8°.

[0278] Example 14. A 2L Buchi reactor was charged with 871 g PDMS (PSF-10000), 50 g PDMS / AEROSIL® RX50 slurry containing 2.9 g (0.5 wt%) AEROSIL® RX50, and 580 g ELASTOLLAN 1190A10 polyurethane. The reactor was purged with nitrogen and stirring was at 200 RPM. The jacket temperature was increased to 240° C. over 60 minutes. Once the reactor temperature reached 200° C., the stirring speed was increased to 500 RPM and the nitrogen flow was turned off. The slurry was stirred at 240° C. for 30 minutes before being discharged hot. After cooling, the slurry was then washed twice with hexane and the microparticles were isolated by vacuum filtration. After drying overnight under vacuum, the microparticles were then sieved through a 150 μm filter. The resulting microparticles had an average particle size (measured by optical microscopy) of 56 μm, a span of 0.59, and an angle of repose of 32.4°.

[0279] Example 15. Polypropylene microparticles were produced in a Haake small-scale twin-screw extruder with a high shear rotor. The carrier fluid was PDMS oil with a viscosity of either 30,000 cSt or 60,000 cSt at room temperature. The concentrations of the components in the final mixture in the extruder are shown in Table 15. The order of addition of the components to the extruder was either (a) carrier fluid was added to the extruder, brought to temperature, and then room temperature polymer pellets were added to the heated carrier fluid in the extruder, or (b) polymer pellets were added to the extruder, brought to temperature, and then room temperature carrier fluid was added to the molten polymer in the extruder. The polypropylene pellets were added at a solids loading of 30% (i.e., 18 g polypropylene in 60 g PDMS). The polypropylene used was PP D115A polypropylene homopolymer available from Baskem USA. At either 225°C or 250°C (see Table 14), the extruder was operated at about 200 rpm for 30 minutes. The mixture was then discharged from the extruder onto a cold surface to allow rapid cooling. The torque of the extruder system was measured during heating, at temperature, and during cooling. The resulting mixture was then washed three times with 300 mL of heptane and filtered through a 90 mm WHATMAN® #1 paper filter (available from SigmaAldrich) to separate the polypropylene particles from the carrier fluid. The particles were then air-dried overnight in an aluminum pan in a fume hood. The dried polypropylene particles were characterized for morphology using SEM micrographs and for size using a Malvern MASTERSIZER™ 3000 Aero S particle size analyzer. Differential scanning calorimetry (DSC) was used to evaluate thermal properties to determine melting and crystallization temperatures. Inductively coupled plasma (ICP) determined the residual silicone oil present on the particles.

[0280] In this example, the powder flow of the fine particles was characterized through sieving and angle of repose measurement. The sieving yield of the fine particles was determined by passing a certain amount of particles through a 250 mm American standard sieve (ASTM E11) and determining the mass fraction of the fine particles that passed through the sieve relative to the total amount of fine particles. The sieve was used manually without any specific condition of the force duration. The angle of repose measurement was performed using a Hosokawa Micron Powder Characteristics Tester PT-R using ASTM D6393-14 "Standard Test Method for Bulk Solids Characterized by Carr Indices". The results are listed in Table 14.

[0281] SEM micrographs show smooth circular particles with a fairly broad particle size distribution. The particles were selectively laser sintered in a single layer on a Sharebot SnowWhite SLS printer. The particles made with 30,000 cSt oil required higher laser power to produce a robustly sintered single layer versus the 60,000 cSt oil particles. The particles made with 60,000 cSt oil showed extreme edge curl as the laser power was increased.

[0282] [Table 14]

[0283] Example 16. Polyamide 12 microparticles were produced in a 25 mm twin screw extruder (Werner & Pfleiderer ZSK-25). The carrier fluid was PDMS oil with a viscosity of 60,000 cSt at room temperature. The concentrations of the components in the final mixture in the extruder are shown in Table 15. The polymer pellets were added to the extruder, brought to temperature, and then the preheated carrier liquid in which the silica nanoparticles were dispersed was added to the molten polymer in the extruder. Other operating parameters are shown in Table 15. The mixture was then discharged into a container and allowed to cool to room temperature over several hours. Light scattering particle size data is also provided in Table 15.

[0284]

Table 15

[0285] Thus, the present invention is well adapted to attain the objects and advantages set forth above, as well as the advantages inherent therein. The specific embodiments disclosed above are merely illustrative, and the invention may be modified and practiced in different but equivalent manners apparent to those skilled in the art having the benefit of the teachings herein. Furthermore, no limitation is intended to the details of construction or design shown herein, other than as set forth in the following claims. Thus, it will be apparent that the specific exemplary embodiments disclosed above may be altered, combined or modified, and all such variations are considered within the scope and spirit of the invention. The invention illustratively disclosed herein may be practiced in the absence of any element not specifically disclosed herein and / or any element disclosed herein. Although the compositions and methods are described in terms "comprising," "containing," or "including" various components or steps, the compositions and methods may also "consist essentially of" or "consist of" various components and steps. All numbers and ranges disclosed above may vary somewhat. Whenever a numerical range with a lower and upper limit is disclosed, any number within that range and any included range is specifically disclosed. In particular, all ranges of values ​​disclosed herein (in the form "from about a to about b," or equivalently "approximately a to b," or equivalently "from approximately a b") should be understood to describe all numbers and ranges encompassed within the broad range of values. Also, the terms in the claims have their plain and ordinary meaning unless expressly and unambiguously defined by the patentee. In addition, when used in the claims, the indefinite article "a" or "an" is defined herein to mean one or more than one of the elements it introduces. Yet another aspect of the present invention may be as follows. 〔1〕 1. A composition comprising: A composition comprising particles comprising a thermoplastic polymer and an emulsion stabilizer associated with an outer surface of said particles, said particles having a circularity of from about 0.90 to about 1.0. 〔2〕 The composition of claim 1, wherein the emulsion stabilizer comprises nanoparticles, at least some of the nanoparticles being embedded in the outer surface of the particle. 〔3〕 The composition according to claim 1, wherein at least some of the particles have voids therein that contain the emulsion stabilizer at the void / thermoplastic polymer interface. 〔4〕 The composition according to [3] above, wherein the void contains a dispersion medium having a viscosity of 1,000 cSt to 150,000 cSt at 25°C. 〔5〕 The composition according to [4], wherein the dispersion medium is selected from the group consisting of silicone oil, fluorinated silicone oil, perfluorinated silicone oil, polyethylene glycol, alkyl-terminated polyethylene glycol, paraffin, liquid petrolatum, mink oil, turtle oil, soybean oil, perhydrosqualene, sweet almond oil, calophyllum oil, palm oil, pearl oil, grape seed oil, sesame oil, corn oil, rapeseed oil, sunflower oil, cottonseed oil, apricot oil, castor oil, avocado oil, jojoba oil, olive oil, cereal germ oil, esters of lanolin acid, esters of oleic acid, esters of lauric acid, esters of stearic acid, aliphatic esters, higher fatty acids, aliphatic alcohols, polysiloxanes modified with fatty acids, polysiloxanes modified with aliphatic alcohols, polysiloxanes modified with polyoxyalkylenes, and any combination thereof. 〔6〕 The composition of claim 1, further comprising elongated structures on the surface of the particles, the elongated structures comprising the thermoplastic polymer, and the emulsion stabilizer associated with an outer surface of the elongated structures. 〔7〕 The composition described in [1], wherein the emulsion stabilizer forms a coating that covers at least 25% of the surface of the particles. 〔8〕 The thermoplastic polymers include polyamides, polyurethanes, polyethylene, polypropylene, polyacetals, polycarbonates, polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polytrimethylene terephthalate (PTT), polyhexamethylene terephthalate, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyesters (e.g., polylactic acid), polyethers, polyethersulfones, polyetheretherketones, polyacrylates, polymethacrylates, polyimides, acrylonitrile butadiene styrene (ABS), polyphenylene sulfide, vinyl polymers, polyarylene ethers, polyarylene sulfides, polysulfones, polyetherketones, polyamideimides, polyetherimides, polyetheresters, copolymers containing polyether blocks and polyamide blocks (PEBA or polyether block amides), grafted or non-grafted. The composition according to the above-mentioned [1], wherein the polymerizable compound is selected from the group consisting of a functionalized thermoplastic polyolefin, a functionalized or non-functionalized ethylene / vinyl monomer polymer, a functionalized or non-functionalized ethylene / alkyl (meth)acrylate, a functionalized or non-functionalized (meth)acrylic acid polymer, a functionalized or non-functionalized ethylene / vinyl monomer / alkyl (meth)acrylate terpolymer, an ethylene / vinyl monomer / carbonyl terpolymer, an ethylene / alkyl (meth)acrylate / carbonyl terpolymer, a methyl methacrylate-butadiene-styrene (MBS) type core-shell polymer, a polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymer, a chlorinated or chlorosulfonated polyethylene, a polyvinylidene fluoride (PVDF), a phenolic resin, a poly(ethylene / vinyl acetate), a polybutadiene, a polyisoprene, a styrenic block copolymer, a polyacrylonitrile, a silicone, and any combination thereof. 〔9〕 The composition described in [1], wherein the thermoplastic polymer is a first thermoplastic polymer and the particles further comprise a second thermoplastic polymer and a compatibilizer. 〔10〕 The composition according to [1], wherein the particles have a D10 of about 0.5 μm to about 125 μm, a D50 of about 1 μm to about 200 μm, and a D90 of about 70 μm to about 300 μm, and D10 < D50 < D90. 〔11〕 The composition according to [1], wherein the particles have a diameter span of about 0.2 to about 10. 〔12〕 The composition according to [1], wherein the particles have a Hausner ratio of about 1.0 to about 1.5. 〔13〕 The composition according to [1], wherein the nanoparticles include particles selected from the group consisting of oxide nanoparticles, carbon black, polymer nanoparticles, and any combination thereof. 〔14〕 A composition comprising: Particles containing a thermoplastic polymer and an emulsifying stabilizer embedded in the outer surface of the particles, wherein the particles have a circularity of about 0.90 to about 1.0, and at least some of the particles have voids containing the emulsifying stabilizer at the interface of the voids / thermoplastic polymer inside. 〔15〕 A method comprising: Mixing a mixture comprising a thermoplastic polymer, a dispersion medium immiscible with the thermoplastic polymer, and an emulsifying stabilizer at a temperature above the melting point or softening temperature of the thermoplastic polymer and at a shear rate high enough to disperse the thermoplastic polymer in the dispersion medium. Cooling the mixture to below the melting point or softening temperature of the thermoplastic polymer to form solidified particles containing the thermoplastic polymer and the emulsifying stabilizer associated with the outer surface of the solidified particles. Separating the solidified particles from the dispersion medium. 〔16〕 The method according to

[15] , wherein the emulsifying stabilizer contains nanoparticles, and at least some of the nanoparticles are embedded in the outer surface of the solidified particles. 〔17〕 The method according to

[15] , wherein the emulsifying stabilizer contains particles selected from the group consisting of oxide nanoparticles, carbon black, polymer nanoparticles, and any combination thereof. 〔18〕 The method according to

[15] , wherein the solidified particles further include an elongated structure on the surface of the solidified particles, the elongated structure contains the thermoplastic polymer, and the emulsifying stabilizer is associated with the outer surface of the elongated structure. 〔19〕 The method according to

[15] , wherein the emulsifying stabilizer is present in the mixture at 0.01 wt% to 10 wt% based on the weight of the thermoplastic polymer. 〔20〕 The method according to

[15] , wherein the thermoplastic polymer is present in the mixture at 5 wt% to 60 wt% of the mixture.

Claims

1. 1. A method comprising: shearing a mixture comprising a thermoplastic polymer, a dispersion medium that is immiscible with the thermoplastic polymer, and an emulsion stabilizer at a temperature above the melting point or softening temperature of the thermoplastic polymer and at a shear rate to disperse the thermoplastic polymer as molten droplets in the dispersion medium in the presence of the emulsion stabilizer; cooling the mixture below the melting point or softening temperature of the thermoplastic polymer to form solidified particles comprising the thermoplastic polymer and the emulsion stabilizer associated with an outer surface of the solidified particles; and separating the solidified particles from the dispersion medium, wherein the emulsion stabilizer comprises a plurality of nanoparticles and the solidified particles have a D50 of 25 μm to 100 μm.

2. The method of claim 1 , wherein at least some of the nanoparticles are embedded in the outer surface of the solidified particles.

3. 10. The method of claim 1, wherein the nanoparticles are selected from the group consisting of oxide nanoparticles, carbon black, polymeric nanoparticles, and any combination thereof.

4. The method of claim 1, wherein the emulsion stabilizer is present in the mixture at 0.01% to 10% by weight based on the weight of the thermoplastic polymer.

5. The method of claim 1, wherein the thermoplastic polymer is present in the mixture at from 5% to 60% by weight of the mixture.

Citation Information

Patent Citations

  • Production of polyurethane and exactly spherical polyurethane particle

    JP1993070539A

  • Method for fine particulate colored resin production, fine particulate color resin and method for article coloration

    JP2002275272A

  • Producing an item by the selective fusion of polymer powder layers

    US20110293918A1

  • Emulsion method for the manufacture of ultra-fine spherical polymer particles

    US20180044484A1

  • Process for forming a powder

    WO2019083877A1